Functional characterization of CnAGAL2, a key α-galactosidase involved in postharvest endosperm thickening of coconut (Cocos nucifera L.) - Jian Wang; Fan-jing Zhang; Fang Liu; Yu-ping Man; Shi-biao Liu; Yan-chang Wang; Dong-dong Li (Postharvest Biology and Technology, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Effects of sampling strategy, geographical origin, and soil on stable isotopes and multi-elements for the traceability of Chinese PGI oranges - Jiahui Wu; Hao Deng; Guang Wu; Hanyi Mei; Karyne M. Rogers; Yurong Huang; Shengzhi Shao; Chunlin Li; Ping Wang; Jing Nie; Yuwei Yuan; Yongzhi Zhang (Food Control, 2026)

Chemical constituents from the fruits of Hypericum patulum and their chemotaxonomic significance - Xue Liu; Jing-Yi Xue; Jian-Ping Yang; Li Jiang; Yang Wang; Xue Ma; Lin Tian; Yong-Jun Li (Biochemical Systematics and Ecology, 2026)

Synergistic dual-site passivation via ionic liquid engineering for efficient and stable deep-red CsPbI₃ QLEDs - Xiaoke Li; Jinjian Lu; Rui Han; Xiaoqing Jing; Yuyu Zhang; Jintao Wang; Ren Sheng; Ping Chen (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Object preference versus novelty preference: The importance of object selection and recommendations for the Novel Object Recognition test in mice - Yuan Yuan; Jing Li; Xiaoying Gu; Shuangshuang Ye; Yuanze Li; Zhuangfei Chen; Ping Ren; Yu Fu (Applied Animal Behaviour Science, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Selective enrichment and metabolic characterization of caproate-producing microbes from Baijiu Huangshui - Guida Zhu; Zhangyi Wei; Zhiye Li; Jing Yu; Qiuxiang Tang; Ping Song (Food Bioscience, 2026)

Genome-wide identification of the cystatin gene family in Japanese flounder (Paralichthys olivaceus) and functional characterization of PoCystatin B and PoCystatin C - Xiangru Li; Ping Han; Yadong Xue; Wenxiaoman Wang; Xiaoxuan Xiang; Xiumei Liu; Jianming Chen; Jing Chang; Xubo Wang (Fish & Shellfish Immunology, 2026)

Crustal anisotropic velocity structure beneath California constrained by P and PmP traveltimes: Implications for fluid-promoted creeping along the central San Andreas Fault - Jing Chen; Tianjue Li; Xiao Xiao; Shucheng Wu; Yiming Bai; Guoxu Chen; Bingfeng Zhang; Mijian Xu; Ping Tong (Earth and Planetary Science Letters, 2026)

A coupled model for simultaneous consolidation and decontamination in heavy metal-laden sediments dewatered by PHDs-VP - Jinxin Sun; Ping Wang; Chuanxun Li; Lijun Han; Saiou Fu; Jing Nie; Jiangshan Li (Computers and Geotechnics, 2026)

Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

Viable lactic acid bacteria across the production-food-gut continuum: Multi-stress adaptation and robustness engineering - Jing Cui; Jiahui Li; Meijuan Ran; Qi Chen; Jiehong Fang; Jiankang Jiang; Qing Cao; Ping Li; Han Jiang; Qing Gu (Trends in Food Science & Technology, 2026)

Shaking table test and numerical simulation of dynamic interaction for single pile-soil-structure model - Lei Yu; Zhen-Dong Cui; Li-Ping Jing; Gang Wang (Soil Dynamics and Earthquake Engineering, 2026)

Aberrant Gamma Oscillations in Parkinson’s Disease - Bing-Yu Li; Ruo-Yu Li; Rong-Hua Hong; Yun-Ping Song; Ling-Jing Jin (Neuroscience Bulletin, 2026)

Making waves: Impaired osmotic reserve by chemical exposure amplifies vulnerability of estuarine organisms to climate-driven salinity shifts - Ruting Yang; Dali Wang; Yao-Ping Wang; Muting Yan; Huizhen Li; Jing You (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Dimefluthrin-induced multigenerational endocrine toxicity in zebrafish (Danio rerio) offspring via parental exposure - Wei-Guo Wang; Rui-Rui Li; Ming-Jun Yang; Jing-Ying Hu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Comprehensive life-cycle assessment of a hybrid renewable energy system–powered decentralized sewage treatment system in cold and rural Inner Mongolia - Shangbin Ma; Ping Miao; Shugang Guo; Yaoting Hu; Hongli Ma; Pengyu Li; Pengfei Cao; Dawen Gao; Jing Luo; Jianguo Liu; Tianlong Zheng (Journal of Water Process Engineering, 2026)

Multi-phase fate and removal mechanism of acetamiprid in a planted coastal wetland mesocosm system: A ‘dual-engine’ perspective - Li Lu; Jing Zhao; Yufei Dai; Xin Luo; Zengyuan Niu; Ping Wang; Xiulin Wang; Keqiang Li (Journal of Hazardous Materials, 2026)

Long-term groundwater arsenic exposure is associated with altered arsenic methylation capacity and gut microbiota composition in a rural Chinese population - Tingchao He; Jing Liu; Yanyan Li; Nobutaka Ohgami; Xiaoyong Wei; Tingting Peng; Xiaojia Zhang; Ruijun Zhang; Juan Du; Yuqi Deng; Hua Jiang; Ping Zhang; et al. (Journal of Hazardous Materials, 2026)

Benzophenone-2 disrupts craniofacial cartilage development via esr2a-Dependent inhibition of endothelin signaling in zebrafish larvae - Zhuoyi Xie; Keying Li; Xiaomai Zhou; Qiuchen Wu; Xiangrong Zhou; Ping Zeng; Jing Li; Qiao Niu; Zhipeng Qi; Xinying Zhao; Weiyi Song (Environmental Research, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

Source-specific oxidative potential and health risks of PM2.5-bound toxic elements in Xiamen Port: Insights into ship emission contributions - Si-Min Zhao; Qi-Yu Miao; Jia-Min Li; Xin-Ye Wu; Bing-Qi Jiang; Li-Xiong He; Yi-Jing Liu; Zhi Huang; Chung-Shin Yuan; Shui-Ping Wu (Atmospheric Pollution Research, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Early Miocene Populus L. Fossils Reveal the Northwestward Expansion of the East Asian Summer Monsoon Into Eastern Qaidam - Zhen‐Dong Cao; San‐Ping Xie; Jing‐Nan Huang; Yun‐Zhe Zhang; Zi‐Yi Li; Si‐Hang Zhang; De‐Fei Yan (Journal of Biogeography, 2026)
Aim The evolution of the East Asian Summer Monsoon (EASM) is critical for understanding Asian biodiversity and ecosystem stability. While models and geological records suggest the EASM reached the Qaidam Basin during the Miocene, macrofossil evidence remains scarce. We aimed to test the hypothesis of a northwestward monsoon expansion using newly discovered Populus fossils as bioclimatic indicators. Location Wulan Basin, northeastern Tibetan Plateau, Qinghai Province, China. Taxon Angiosperms (Salicaceae: Populus L.). Methods We conducted morphological analyses on leaf fossils and identified their Nearest Living Relative (NLR). By establishing correlations between the leaf traits of the NLR and modern climatic factors, we reconstructed the paleoclimate of the Wulan Basin. Furthermore, we employed Species Distribution Modelling (MaxEnt) to simulate the potential range of this lineage under Early Miocene conditions to explore monsoon‐driven habitat shifts. Results The late Early Miocene fossils from the Wulan Basin are morphologically most similar to the extant Populus davidiana , a species characteristic of temperate, semi‐humid environments. The presence of this lineage indicates that the Wulan Basin—currently an arid region—experienced significantly higher precipitation and a temperate semi‐humid climate during the Early Miocene. MaxEnt modelling reveals that the suitable bioclimatic envelope for this Populus group extended much further northwest than its modern range, providing a potential biological signal of enhanced moisture transport into the interior of East Asia. Main Conclusions The occurrence of Populus fossils in the Wulan Basin provides a preliminary biological indicator for the northwestward expansion of the EASM into the northeastern Tibetan Plateau during the late Early Miocene, although corroboration from additional proxy records and localities is still needed. This climatic shift, likely driven by the phased uplift of the Tibetan Plateau, transformed the regional hydrological cycle and facilitated the migration of mesic woody taxa into Asia's interior. Our findings highlight the profound impact of tectonic‐monsoon interactions on historical plant distributions.

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Differential effects of a novel mesoionic insecticide, triflumezopyrim, on Apis mellifera and Apis cerana - Mei-Ling Zhang; Shu-Wei Wang; Wen-Min Li; Sasiprapa Krongdang; Yan-Yan Wu; Ping-Li Dai; Shan-Shan Li; Jing Gao (Journal of Hazardous Materials, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Multi-dimensional analysis revealing the mechanism of T-2 toxin driving liver fibrosis: integration of network toxicology, machine learning, experimental verification, and molecular docking - Lichun Qiao; Shaoteng Shi; Liangjia Wang; Muhammad Aftab Shafiq; Jing Tang; Miaoqian Li; Ping Wan; Jingxuan Zhou; Xulei Dai; Jing Han; Yijie Guo (Chemico-Biological Interactions, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Limosilactobacillus reuteri LR-99 Modulates Gut Microbiota and Core Symptoms in Children with Autism Spectrum Disorder: A Single-arm Pilot Study - Kai Gong; Ziying Xie; Ping Zhang; Jing Xu; Jiangfeng Huang; Xingyu Li; Lihong Huang (Probiotics and Antimicrobial Proteins, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Continental Jurassic/Cretaceous transition in Northeast China: Stratigraphic and spatiotemporal constraints from the Hailar Basin and adjacent areas - Chong-Yang Chen; Li-Ping Yao; Pu-Jun Wang; Hai-Bo Wu; Jing-Sheng Li; Yan-Ping Hou; Yun-Fei Xue; Shu-Qin Zhang (Cretaceous Research, 2026)

In vitro nephroprotective indolizidine alkaloids from marine-derived Streptomyces sp. KIB629 - Xiaowei Guo; Lei Wang; Xin He; Bing-Yi Xu; Jun-Jie Zhang; Jian-Ping Huang; Wei Li; Sheng-Xiong Huang; Jing Yang; Ya-Tuan Ma (Natural Product Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Unified strength prediction formula for axially compressed FRP-confined concrete stub columns with different cross sections - Wei-Jie Li; Jing Sun; Wei-Ping Zhao; Jia-Qi Yang; Yi-Yan Lu (Engineering Structures, 2026)

Quantifying scale effects in pile scour depth prediction for field applications via interpretable machine learning - Yang-Xin Zhou; Qing-Kai Song; Wen-Gang Qi; Li-Jing Yang; Xiao-Bing Lu; Fu-Ping Gao (Coastal Engineering, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Uncovering the Community Structure and Adaptive Characteristics of Soil Protists Across Natural, Semi‐Natural and Highly Degraded Habitats - Shi‐wei Feng; Xiaonan Wang; Ping Wen; Jing‐li Lu; Zhuo‐hui Wu; Xinzhu Yi; Wen‐sheng Shu; Jie‐Liang Liang; Pu Jia; Jin‐tian Li (Environmental Microbiology, 2026)
Protists are vital to soil ecological functions. However, their diversity and community patterns remain poorly characterised across habitats. This study investigated protists in 270 samples spanning five terrestrial ecosystems: natural (forest, grassland, desert), semi‐natural (farmland) and highly degraded (mine wasteland). The species richness of protists and the consumer functional group were highest in farmland and lowest in mine wasteland. We demonstrated that habitat type ( R partial Mantel = 0.291) exerted stronger effects on protistan communities than geographic distance ( R partial Mantel = 0.072). While α‐diversity drivers varied among habitats (e.g., total phosphorus (TP) was only positive in farmland and forest), β‐diversity was consistent and significantly correlated with mean annual temperature (MAT), mean annual precipitation (MAP), aridity index (AI) and moisture. We identified nine potential ecological groups of protists, reflecting their adaptive differentiation. To explore community assembly, a null model was conducted, revealing that stochastic processes dominated all habitats. Furthermore, co‐occurrence networks of protists, prokaryotes and fungi showed lower modularity and stability in mine wasteland compared with other habitats, indicating co‐occurrence patterns may be more specialised under resource limitation. Collectively, our results highlight the importance of habitat type in shaping protistan communities, suggesting that protists can be predictably regulated in degraded environments.

Impact of macroalgae farming on the carbonate system and biogenic sulfur dynamics in Sansha Bay, China - Ping Wang; Zheng-Xin Hu; Yu Xin; Bing-Han Li; Lu Han; Shu-Hang Dong; Chun-Ying Liu; Tao Liu; Jing-Wen Hu; Jiang-Chen Gong; Gui-Peng Yang (Marine Pollution Bulletin, 2026)

Dual-emitting persistent luminescence-based Ratiometric Aptasensor without complementary-strand and in-situ excitation for accurate detection of bioactive Lactoferrin - Yan-Jun Jin; Jing-Xuan Guo; Zhu-Ying Yan; Li-Jian Chen; Xiu-Ping Yan; Xu Zhao (Food Chemistry, 2026)

Distribution, source, and pollution risk assessment of heavy metals in the coastal sediments of the northern South China sea - Wen Yu; Yuqing Fan; Qinghua Chen; Jing Yang; Xin Li; Wei Huang; Kun Yue; Liuyi Zhang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2026)

First report of mitochondrial genomes in Hydryphantoidea: novel genomes, evolution rate, and gene rearrangement patterns in two water mites (Acari: Hydrachnidia) - Xin-Yao Gu; Ping Li; Hao Zhong; Hai-Tao Li; Jian-Jun Guo; Gang Li; Tian-Xing Jing (Experimental and Applied Acarology, 2026)

Activating FcγRI inhibits RIG-I-mediated host antiviral innate immunity by FGR during PRRSV-ADE infection - Peng-li Xu; Yi-han Li; Fa-hao Li; Shi-jie Zhao; Wen Li; Jing Chen; Ping-an Xia; Yi-na Zhang (Veterinary Microbiology, 2026)

GmMYB84, a transcription factor, confers cadmium tolerance in soybean via regulation of the phenylpropanoid pathway - Zehua Gong; Jinni Zhao; Jing Xu; Zhichao Zhai; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Plant Science, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Structural heterogeneity and anisotropy beneath Myanmar: Insights into the complex deformation of the Indo-Burma subduction zone - Yiming Bai; Shengji Wei; Jing Chen; Tianjue Li; Bingfeng Zhang; Xiao Xiao; Shucheng Wu; Jiayuan Yao; Yu Wang; Ping Tong (Earth and Planetary Science Letters, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Soil aggregate-mediated dynamics of microbial necromass under contrasting cropland management practices - Wen-Jun He; Jie-Yu Gao; Xin-Xin Jing; Peng Chen; Lu-Ping Ye; Zhi-Guo Li; Yi Liu; Chen-Hao Lyu (Plant and Soil, 2026)

Surveillance reveals a prevalent pediatric A(H1N1)pdm09 virus with hemagglutinin substitutions S137P-R142K-V152I that diminish vaccine efficacy - Lifeng Zhao; Jing Wang; Jihong Xu; Jiane Guo; Ping Zhang; Xiaofang Guo; Zhihong Zuo; Ruihong Gao; Li Gao; Jitao Wang (Virus Genes, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Polystyrene-nanoplastics-induced unfolded protein response in monocyte-derived macrophages mediates pulmonary fibrosis via oxidative-stress-dependent IL-6 secretion - Yangxuan Wei; Yulin Wu; Delin Zhu; Jiayu Zhang; Xiaojuan Li; Mingzhu Wang; Xiaohui Cui; Yutong Wu; Di Wen; Jing Zuo; Ping Lv; Haitao Shen (Journal of Hazardous Materials, 2026)

The degradation pathway and removal effectiveness of atrazine in a Photocatalysis–Microorganism combined system in coastal wetlands - Yufei Dai; Jing Zhao; Li Lu; Jingyu Zhang; Mengxue Xing; Haoyu Zhang; Xin Luo; Zengyuan Niu; Ping Wang; Keqiang Li (Journal of Environmental Management, 2026)

Metagenomics reveals potential antimicrobial peptides in Chinese baijiu fermentation - Rubing Du; Xue Li; Yan Xu; Kexin Jing; Ling Ao; Bo Deng; Qing Xu; Ping Song; Jing Yu (Food Microbiology, 2026)

Nematode predation mitigates microbial competition to sustain the plant growth-promoting effect of Streptomyces - Ke-Fan Huo; Jing-Nan Zhang; Elly Morriën; Ping Liu; Neil B. McLaughlin; Kai-Hong Bai; Zhen-Long Wang; Shi-Xiu Zhang; Lu-Jun Li (European Journal of Soil Biology, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Strength Degradation and Chloride Ion Diffusion Behavior of Concrete Under Simulated Marine Exposure - Shaoping Li; Xiaozhou Zhang; Yaling Zhao; Hongjun Jing; Ping Lyu; Junwei Shan (Journal of Marine Science and Engineering, 2026)
Chloride-induced deterioration is a major threat to the durability of marine concrete structures, especially in tidal and submerged zones. This study simulated these environments by immersing C45 concrete specimens in NaCl solutions (5%, 10%, 15%) under both constant immersion and wet–dry cycles. Compressive strength tests, low-field NMR for pore structure, chloride ion profiling, and SEM-EDS analyses were conducted. A modified chloride diffusion model was developed based on Fick’s second law, incorporating time- and concentration-dependent parameters. The results showed that higher NaCl concentrations and tidal zone exposure significantly accelerated concrete degradation. In the tidal zone, wet–dry cycles led to larger macropore formation, higher chloride penetration, and more severe microstructural damage compared to the submerged zone. Compressive strength initially increased and then declined in high-salinity environments, with strength losses reaching up to 25% under 15% NaCl after 120 days. NMR data confirmed the transformation of micropores and mesopores into macropores, especially in the tidal zone. SEM-EDS analysis revealed decalcification, gypsum formation, and Friedel’s salt accumulation on eroded surfaces. It was determined that chloride ion diffusion behavior in concrete is significantly influenced by the chloride content and diffusion concentration, as well as the exposure zone. The developed model indicates that depth increased over time and with concentration. The proposed diffusion model achieved high fitting accuracy (R2 > 0.97), effectively capturing the effects of erosion age and salt; this makes it a reliable tool for predicting chloride ion ingress in marine concrete, and for supporting service life evaluation and durability design.

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Anthropogenic heat amplification in industrial zones: Unraveling heat stress risk heterogeneity in river-sea dual-core cities - Yujie Li; Jingfu Cao; Mingcai Li; Song Jiang; Jie Yang; Rui Xin; Ping Qu; Jing Chen; Jing Wang (Sustainable Cities and Society, 2026)

Palynological succession in Gzhelian No. 8 Thick Coal of the Taiyuan Formation, Ordos Basin, North China - Hui Zhang; Yun-He Shi; Peng-Shuai Jiao; Bo Pan; Feng Liu; Ming-Li Wan; Jing-Kun Zhang; Hui-Ping Peng (Palaeoworld, 2026)

MsTIFY10a gene from alfalfa negatively regulates drought and salt tolerance in transgenic tobacco - Qi Chen; Yan Zhang; Ying Tian; Jing Xu; Qing-Wen Fu; Zhen-Yi Li; Feng-Ling Shi; Cui-Ping Gao; Zhi-Qiang Zhang (Journal of Plant Physiology, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

PbrRALF5/10 prevents incompatible pollen tube death by reconstructing the methyl-esterified pectin and reactive oxygen species metabolism of pear in vitro - Xiao-Xiong Kong; Tao Chen; Li-Yu Gao; Xu Huang; Xiao Liu; Jing Zhang; Zhi-Ping Zhang; Chun-Lei Wang (Plant Molecular Biology, 2026)

Caffeoylquinic acid derivatives (CQAs) from Daphne gemmata and their antimicrobial activities - Lin Li; Fu-Qiang Song; Ping-Jing Yu; Li-Ping Tang; Xian Li (Natural Product Research, 2026)

Undescribed dihydro- β -agarofuran sesquiterpenoids from the roots of Tripterygium wilfordii - Ya-Lin Hu; Jia-Li Huang; Chong Wang; Wen-Jie Chen; Jing-Yi Huang; Yi-Ping Xie (Natural Product Research, 2026)

Dual-function cytokines as modulators of autophagy: reprogramming inflammatory resolution in severe COVID-19 - Sohrab Khan; Ping Tang; Pingchang Yang; Jing Li; Haiqiang Wu (Inflammation Research, 2026)

Polyprenylated xanthones with potential anti-inflammatory and anti-HIV effects from the stems and leaves of Cratoxylum cochinchinense (Lour.) Blume - Yong Zhang; You-Di Rao; Jing-Su Yu; Jia-Yi Hu; Wen-Hui Hu; Shu-Ri Li; Hui Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Impacts of acidification and warming on carbon sequestration capacity in Pacific oysters: Roles of biosynthesis and biodeposition - Zi-Jing Meng; Cheng-Zhuang Chen; Yu-Qing Ma; Jian-Xue Feng; Ling Liu; Ping Li; Zhi-Hua Li (Aquaculture, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Multi-phase distribution and predictive modeling of polycyclic aromatic hydrocarbons in the East China marginal seas - Zishan Diao; Yiteng Sun; Minggang Zheng; Xue Zhang; Wenpeng Li; Xianyin Ping; Bin Hui; Fanping Zhu; Jing Wang; Shuguang Wang; Xiaohan Zhang; Xianzheng Yuan (Water Research, 2026)

An interpretable machine learning model for predicting p-y curves of monopiles in clay - Biao Li; Wen-Gang Qi; Yi-Fa Wang; Fu-Ping Gao; Lu Jing; Shun-Yi Wang; Ben He (Ocean Engineering, 2026)

Combined neurotoxicity of aged polystyrene microplastics and cadmium in zebrafish: A gut-brain axis perspective - Xue Li; Liqun He; Kexin Jing; Ping Song; Jing Yu (Journal of Environmental Sciences, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Mild magnetic hyperthermia-enhanced perfusion chemotherapy against bladder cancer - Han Jiang; Siqian Li; Hanyong Dong; Jing Wang; Ping Hu; Jianlin Shi (Chemical Engineering Journal, 2026)

Robust immobilization of uranium using biogenic FeS with lignocellulose from green plant waste - Ruoyan Wu; Xiaolin Wang; Siyu He; Minyi Wu; Panyu Li; Pau-Loke Show; Ping Han; Muhammad Hazwan Hamzah; Yongkui Zhang; Jing Chen (Chemical Engineering Journal, 2026)

Enhancement of anaerobic digestion performance of waste activated sludge by sludge-derived alkaline-slow-release mesoporous biochar: Insights into electron transfer, extracellular polymeric substances, and microbial metabolism - Wei Wu; Jing Sun; Qian Ping; Lin Wang; Yongmei Li (Chemical Engineering Journal, 2026)

Anti-epileptic effect of saikosaponin a by inhibiting ferroptosis via the IL-17/Akt/ERK signaling pathway in the temporal lobe epilepsy model - Ping-Ping Li; Wen-Wen Wang; Jing-Tao Wang; Zi-Ao Xu; Xue-Fei Ji; Liao Guan; Lei Ye; Hong-Wei Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

HSPA8 lactylation attenuates neuronal pyroptosis via E3 ligase-mediated NLRP3 degradation after ischemic stroke - Jing Fu; Liang Yu; Nengwei Yu; Ping Ni; Chaohui He; Qiao Chen; Suping Li; Fei Xu (Apoptosis, 2026)

Chemical constituents with potential cytotoxic activities from Cynanchum otophyllum - Jinrun Dong; Deqiong Niu; Ping Xiang; Zhonghai Dao; Jing Li (Natural Product Research, 2025)

RG1.60-based High-damping Response Spectrum for Seismic Analysis of Nuclear Power Plant Structures - Xiao-ying Sun; Peng-xiang Dong; Jian Chen; Tao Wang; Xiao-dan Sun; Li-ping Jing; Yu Liu (Applied Geophysics, 2025)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Structural characterization and oxidative stress modulation activity of an acidic Heteropolysaccharide from Microctis folium - Xiao-lu Liang; Yu-wen Liang; Jing Tian; Fei-fan Mo; Tian-ming Pan; Yan-feng Chen; Xiao-qi Shao; Kun-Ping Li (Carbohydrate Polymers, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Solar-activated ZnS@MXene heterostructure for integrated radioactive wastewater treatment and energy harvesting - Yi-Lin Liu; Ping Cao; Qingyan Zhang; Changgui Guo; Jing Li; Qingyi Zeng (Water Research, 2025)

Impact of per- and polyfluoroalkyl substances structure on oxidative stress and lipid metabolism disruption in HepG2 cells - Xue Li; Kexin Jing; Liqun He; Ping Song; Jing Yu (Toxicology, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

The cotton gene family encoding translationally controlled tumor proteins and the role of GhTCTP5 in salt tolerance - Bo Pang; Jialin Chen; Ping Luo; Ru Zhang; Jing Li; Weiwei Liang; Wenwei Gao; Shengmei Li (Plant Science, 2025)

Effect of apparent pore-fluid compressibility and degree of saturation with atmospheric pressure on wave-induced transient pore pressure response - Wen-Gang Qi; Pei-Qing Zhao; Li-Jing Yang; Mo-Zhen Zhou; Fu-Ping Gao; Dong-Sheng Jeng (Ocean Engineering, 2025)

Sulfur-doped CoFe2O4 as an efficient peroxymonosulfate-activated catalyst for carbamazepine removal: The key role of sulfur and mechanism study - Cong Pan; Xueying Pei; Xinyue Luo; Jing Bao; Ping He; Song Wang; Kaining Li (Journal of Cleaner Production, 2025)

Mixotrophic Chlorella pyrenoidosa biofilm with enhanced biomass production, microalgal activity, and nutrient removal from nutrient-rich wastewater - Xiongwei Wu; Cong Jin; Chiqian Zhang; Ping Li; Jim Junhui Huang; Jing Wu; Jinhua Wu; Zhiqiang Hu (Journal of Environmental Sciences, 2025)

Multi-omics and random forest reveal lipid metabolism disruption and biomarkers in grass carp (Ctenopharyngodon idellus) exposed to 2-methylisoborneol - Huan Han; Jun-Ming Zhang; Kang Li; Justice Frimpong Amankwah; Xiang-Biao Zeng; Zi-Qian Shen; Xi-Chen Jin; Tao-Ying Chen; Jing-Wei Liu; Li-Ping Liu (Environmental Research, 2025)

Z-scheme heterojunction engineered covalent organic polymer for thermodynamically optimized CO2 photoreduction - Jiaxin Rong; Xuejing Li; Qiang Xu; Jingwei Han; Jing Zhang; Ke Ren; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

Modification of oceanic lithospheric mantle by percolated melts sourced from recycled ancient crust: Evidence from Ca Os isotopes of refractory harzburgites - Hui-Chao Rui; Olivier Namur; Dong-Yang Lian; Peng-Jie Cai; Jie Li; Yurisley Valdes-Mariño; Jing-Sui Yang; Hong-Ping He (Chemical Geology, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Corrigendum to ‘Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A’ [Phytochemistry. 222 (2024) 114073] - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li Ping Lin (Phytochemistry, 2025)

Durability and damage mechanisms of electrolytic manganese residue-based grouting materials for seepage prevention in solid waste landfills under simulated service environments - Conggan Xu; Ping Wang; Yifu Xu; Lijun Han; Saiou Fu; Yao Qu; Yongyong Chen; Weiyu Liu; Yaoyi Wang; Zhen Qi; Jing Nie; Xuewen Lei; et al. (Journal of Environmental Management, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

The synergistic enhancement of adsorption for Pb2+ and organic dyes by a chitosan-based hydrogel as a multipollutant adsorbent - Yun Wang; Li-Ping Fang; Chen-Yang Li; Chang-Jing Cheng; Ting Liang; Xing-Bin Lv; Hai-Rong Yu (Journal of Environmental Chemical Engineering, 2025)

All-in-one wearable electronic based on bacterial cellulose composite: Integrating strain sensing and energy harvesting - Ping Sun; Zongxue Gu; Duo Xu; Bin Yu; Hui Sun; Juan Li; Nan Zhou; Jing Li; Keshuai Liu; Yingcun Liu; Chong Gao; Weilin Xu (Chemical Engineering Journal, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Huangqi Guizhi Wuwu Decoction inhibits ferroptosis to improve cyclophosphamide induced immunosuppression through regulation of arachidonic acid metabolism - Li Wang; Fenyun Liu; Qianqian Wan; Yafei Xia; Qi Zhang; Jing Xun; Ping Li; Yuming Wang; Mei Li; Yuhong Bian; Huantian Cui (Journal of Molecular Histology, 2025)

In situ addition of layered double hydroxides promotes sulfate-dependent anaerobic methane oxidation and microbial community shifts in freshwater-influenced mangroves sediments - Jijuan Ding; Fei Liu; Jing Huang; Ping Li; Junmao Zhang; Bo Wu; Longfei Shu; Zhili He; Cheng Wang (Water Research, 2025)

Efficient recovery of spent catalysts in PAO production via annular drainage hydrocyclone: a sustainable approach for fluorinated waste reduction - Wei Zhao; Jian-ping Li; Tong Zhang; Shu Zhu; Ao-song Wei; Dan-hui Yang; Xue-jing Yang; Hua-lin Wang (Journal of Cleaner Production, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Sulfide-based autotrophic denitrification process with efficient nitrogen removal under high salinity stress: Threshold behaviors and recovery enhanced via glutamate supplementation - Kaiyu Zhang; Qaisar Mahmood; Jiayi Lv; Na Liang; Xiaopeng Zhu; Jinye Li; Jing Cai; Ping Zheng (Bioresource Technology, 2025)

Quantifying the major sources of nitrate in PM2.5 in a port city in southeastern China: Perspectives from nitrate dual isotopes and NOx emission inventory - Qi-Yu Miao; Xiang Li; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Xi-Jie Yin (Atmospheric Pollution Research, 2025)

Transcriptome and Metabolome Conjoint Analysis Revealed that PaGLK Affects Photosynthesis and Composition of Root Exudates in Poplar - Xiang-dong Bai; Yu Zheng; Li Cao; Wei Wang; Jing Jiang; Qi-bin Yu; Chuan-ping Yang; Gui-feng Liu (Plant Molecular Biology Reporter, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Gas Hydrate Exploration Using Deep-Towed Controlled-Source Electromagnetics in the Shenhu Area, South China Sea - Jianping Li; Zhongliang Wu; Xi Chen; Jian’en Jing; Ping Yu; Xianhu Luo; Mingming Wen; Pibo Su; Kai Chen; Meng Wang; Yan Gao; Yao Zhang (Journal of Marine Science and Engineering, 2025)
This study presents the first application of a deep-towed transmitter–receiver marine controlled-source electromagnetic (TTR-MCSEM) system for gas hydrate exploration in the Shenhu area of the South China Sea. High-resolution electromagnetic data were acquired along a 13 km transect using dynamic source–receiver offsets and a 500 A transmitter. The results reveal the following: (1) unprecedented near-seafloor resolution (20~100 m) for the precise delineation of hydrate-bearing caprock, surpassing conventional ocean-bottom electromagnetic systems; (2) laterally continuous high-resistivity anomalies (~10 Ω·m) extending from the base of the gas hydrate stability zone to the seafloor, which correlate with seismic bottom-simulating reflector (BSR) distributions and suggest heterogeneous hydrate saturation; and (3) fault-controlled fluid migration pathways that supply hydrate reservoirs and lead to seabed methane seepage at structural highs. Through 2D inversion, we show that the inverted resistivity values (~10 Ω·m) are slightly higher than those obtained from resistivity logs (~5 Ω·m). Saturation values derived from inverted resistivity exhibit remarkable consistency with well-log-based measurements. The high efficiency of the system confirms its potential for the transformative quantitative assessment of hydrate systems, seafloor massive sulfides, and marine geohazards.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Traditional and novel organophosphate esters in atmosphere of greenhouse covered with mulch films: Seasonal variations, partitioning and exposure risks - Fang Zhao; Sinuo Tian; Jing Liu; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Hua Ping; Cheng Li (Journal of Hazardous Materials, 2025)

Kaempferol improves recurrent spontaneous abortion outcomes and prevents oxidative stress damage by inhibiting the NF-kB signaling pathway - Guangli Xu; Huijuan Li; Lei Fang; Jingjing Guo; Chenyu Zhang; Jing Guo; Shuqing Ren; Ping Chen (Food and Chemical Toxicology, 2025)

Bioluminescent fungi-inspired room temperature phosphorescence mycelia - Xin Li; Jin-Xin Ma; Ping Wu; Qian Gao; Hao Wang; Lu-Xin Tang; Feng Peng; Bao-Zhong Lü; Jing Si; Bao-Kai Cui (Chemical Engineering Journal, 2025)

Underrated risk of antibiotic resistance genes dissemination mediated by bioaerosols released from anaerobic biological wastewater treatment system - Na-Na Han; Xue-Ping Wang; Jing-Ao Jin; Wen-Hui Li; Wen-Ya Yang; Nian-Si Fan; Ren-Cun Jin (Water Research, 2025)

Effects of exogenous mineral silicon on physiological characteristics and arsenic uptake and transport in rice - Jing Han; Qihao He; Mingjing Lei; Ke Li; Yufei Zhou; Wenmin Li; Ying Xiao; Fan Zhang; Chang Sun; Jieying Wang; Jian Zhu; Zhiming Liu; et al. (Journal of Hazardous Materials, 2025)

GWAS and GS analysis revealed the selection and prediction efficiency for yield, plant morphological, and fiber quality in Gossypium barbadense - Tao Yang; Honggang Wang; Jikun Song; Kang Zhao; Bo Pang; Yongpan Wang; Ping Luo; Weiwei Liang; Shunyu Shi; Jie Wang; Yifeng Lin; Jing Li; et al. (Theoretical and Applied Genetics, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

Effects of early-life F-53B exposure on thyroid function in juvenile rats: The role of the cAMP signaling pathway - Shen-Pan Li; Wen-Hui Zhao; Jing Zhang; Wen-Ting Jiang; Jia-Yi Zhu; Yi-Xin Luo; Ping Xiang; Michael Bloom; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Nitrification inhibitor shifts the composition of soil microbial communities and increases N utilization potentials in wheat soil under elevated CO2 concentration - Jing Yang; Xiaxuan Lai; Yan Wang; Lifeng Guo; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Plant and Soil, 2025)

Health risk assessment of heavy metal emissions from on-road vehicles in a metropolitan area in southeastern China - Qi-Yu Miao; Zhe-Nan Wen; Shui-Ping Wu; Jun Hu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu (Journal of Atmospheric Chemistry, 2025)

A safety and absolute activity measurement method for Phi29 DNA polymerase based on chemiluminescent detection of dATP consumption - Xuefeng Wang; Ping Gui; Xiao Li; Feng Lu; Wei Jing; Changlong Li; Zelin Lu; Yanna Lin; Huancai Yin; Haichao Li; Fuqiang Ma (Analytica Chimica Acta, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

The transcription factor CsPAT1 from tea plant (Camellia sinensis) is involved in drought tolerance by modulating phenylpropanoid biosynthesis - Jing-Wen Li; Ping Zhou; Zhi-Hang Hu; Ai-Sheng Xiong; Xing-Hui Li; Xuan Chen; Jing Zhuang (Journal of Plant Physiology, 2025)

Enhanced activation of peroxymonosulfate by nickel sulfide with sulfur vacancies for ultrafast organic pollutants degradation: Roles of active sites and mechanism - Cai-Wu Luo; Liang Jiang; Xian-Feng Li; Qiang-Mao Wan; Tian-Jiao Jiang; Sen-Ping Mao; Jing-Qian Guo; Run-Ze Zhao; Chao Xie (Environmental Pollution, 2025)

Gradient-Structured sodiophilic skeleton integrated with spatial confinement effect Enables high-rate and ultra-stable Na metal batteries - Fang-Yu Tao; Dan Xie; Wan-Yue Diao; Chang Liu; Godefroid Gahungu; Wen-Liang Li; Jing-Ping Zhang (Chemical Engineering Journal, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Minor protopanaxadiol type sapogenins from the alkali hydrolysate of stems-leaves of Panax notoginseng - Cong-Cong Jing; Jing-Min Wang; Pei Wang; Lin Guo; Shu-Min Zhang; Ke Liu; Zhen-Yuan Li; Hua-Ying Fan; Ze-Ping Xie (Natural Product Research, 2025)

ABA-INSENSITIVE 4 promotes nicotine biosynthesis under high light in Nicotiana attenuata - Bo Lei; Yan Mao; Huina Zhao; Jing Yu; Bing Wang; Ping Li; Xiangyang Hu (Plant Science, 2025)

Boosting photocatalytic ozonation activity through F or I doping in g-C3N4: A trade-off between stability and performance - Weirui Chen; Weijie Chen; Yimin Luo; Yanqi Feng; Xukai Li; Jing Wang; Ping Li; Liying Bin; Bing Tang; Laisheng Li (Journal of Environmental Chemical Engineering, 2025)

Preparation of electrospun ZIF-67/PVP/PVDF composite nanofiber membranes for efficient tetracycline removal from water - Shaolin Deng; Jing Zhang; Xiaolin Yue; Ping Li; Anhong Li; Zehua Huang; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Lactic acid/tartaric acid-maltitol antibacterial activity against spoilage bacteria and prevention of yellowing and wilting in spinach and oilseed rape - Dengyi Ye; Jing Ren; Yanan Zhang; Xiyu Wang; Jiali Guo; Bing Li; Quanliang Li; Yanjun Chen; Ping Chen; Biying Zhang (Food Chemistry, 2025)

Highly efficient flame-retardant plasticizers for flexible poly(vinyl chloride) via the synergism of integrated isocyanurate, DOPO and poly(ε-caprolactone) - Xing-Ping Zhang; Jing Zhao; Xing-Hao Wang; Yu Chen; Hai-Chao Li; Liang Yang (Chemical Engineering Journal, 2025)

Experimental investigation of scour effects on regular and breaking wave loads on a monopile - Biao Li; Wen-Gang Qi; Fu-Ping Gao; Ben He; Li-Jing Yang (Coastal Engineering, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Effects of geosmin and 2-methylisoborneol exposure on the gill transcriptome of Nile tilapia (Oreochromis niloticus) - Jun-Ming Zhang; Huan Han; Sow Abdoul Gadiri; Wannapha Kitrattana; Zhong-Qian Wang; Jing-Wei Liu; Kang Li; Li-Ping Liu (Aquaculture International, 2025)

Targets and Potential Mechanism of Chondroitin Sulfate A-selenium Nanoparticle on Kashin-Beck Disease Chondrocytes - Huan Deng; Feidan Deng; Xinyue Wen; Yude Jiang; Abebe Feyissa Amhare; Lichun Qiao; Miaoqian Li; Ping Wan; Jun Wang; Jing Han (Biological Trace Element Research, 2025)

Dietary supplementation of Litsea cubeba oil promotes growth and intestinal immunity in GIFT tilapia - Fu-Yan Chen; Ying Bai; Gan Yang; Han-Jing Yan; Liu-Yang Li; Zhi-Mou Liu; Ju-Ping Wen; Zhen-Bin Wang; Jun-Hong Xia; Meng-Ling He (Aquaculture, 2025)

Sus scrofa RNase L inhibits PRRSV replication by activation of type I IFN signaling pathway and apoptosis - Xiangju Wu; Xiaoyan Cong; Ping Jiang; Mingming Zhou; Ying Yu; Dandan Jiang; Yue Hu; Juntong Li; Jinxia Zhang; Ying Cao; Haowen Zhang; Yijun Du; et al. (Veterinary Microbiology, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Genomic analysis of Isoptericola halotolerans SM2308 reveals its potential involved in fucoidan degradation - Yu-Qi Zhang; Qi Yuan; Ji-Qing Liu; Xiao-Chen Liang; Jing-Ping Wang; Wen-Xin Jiang; Ping-Yi Li (Marine Genomics, 2025)

Molecular weight distribution and structure analysis of phlorotannins in Sanhai kelp (Saccharina japonica) and evaluation of their antioxidant activities - Jing Zhang; Long Xing; Wenya Meng; Xiaojie Zhang; Jing Li; Ping Dong (Food Chemistry, 2025)

Liubao insect tea polyphenols ameliorate DSS-induced experimental colitis by protecting intestinal barrier and regulating intestinal microbiota - Xinyu Feng; Yanwen Chen; Lina Luo; Zhoutao Fang; Shicheng Ma; Zhongxia Li; Jing Huang; Yani Pan; Helin Lv; Shuying Gong; Xiaodong Zheng; Fangyuan Fan; et al. (Food Chemistry, 2025)

Long-term no tillage straw mulching increased soil water and nitrogen storage in dryland wheat on the Loess Plateau, but may increase dissolved organic nitrogen leaching - Xinrui Shi; Xiaowen Liu; Jianyun Jing; Yan Zhang; Ping Li; Yuzheng Zong; Dongsheng Zhang; Xingyu Hao (Field Crops Research, 2025)

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

The P-wave velocity and azimuthal anisotropy structure of southeastern margin of the Tibetan Plateau from adjoint-state traveltime tomography - Xuezhen Zhang; Xiaodong Song; Jing Chen; Lei Zhang; Ping Tong; Yan’e Li (Science China Earth Sciences, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Study on the feasibility of buckwheat as a trap plant for flower thrips (Frankliniella intonsa) in sunflower field - Hui Qu; Jing Chang; Ze-Run Chuai; Wen-Bing Zhang; Jian Zhang; Jun Zhao; Hai-Ping Li (Journal of Pest Science, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Identification of the Shuanglongtan tectonic mélange (ca. 1.7–1.5 Ga) in the southwestern Yangtze Block and it’s tectonic implications - Jun-Ping Liu; Zai-Bo Sun; Xiao-Hu He; Jiang-Tai Zhao; Shi-Jun He; Ling-Jing Bi; Wei-Ke Li (Precambrian Research, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

Characterizing Chinese saffron Origin, Age and grade using VNlR hyperspectral imaging and Machine learning - Jiahui Wu; Jing Nie; Hao Hu; Xinyue Xu; Chunlin Li; Hongkui Zhou; Peishi Feng; Hanyi Mei; Karyne M. Rogers; Ping Wang; Yuwei Yuan (Food Research International, 2025)

Mantle induced hydration and oxidation of intracontinental granite sources in the North China Craton - Chuan-Mao Yang; Yi-Gang Xu; Xiao-Ping Xia; Jin-Hui Yang; Xiao-Long Huang; Christopher J. Spencer; Jin-Feng Sun; Ze-Xian Cui; Meng-Jing Li; Wan-Feng Zhang; Qing Yang (Earth and Planetary Science Letters, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Lactobacillus acidophilus JYLA-126 Ameliorates Obesity-Associated Metabolic Disorders by Positively Regulating the AMPK Signaling Pathway Through the Gut-Liver Axis - Ping Li; Xia He; Enxu Feng; Jing Wei; Huaijun Tu; Tingtao Chen (Probiotics and Antimicrobial Proteins, 2025)

Cadmium translocation combined with metabolomics analysis revealed potential mechanisms of MT@MSN-CS and GSH@MSN-CS in reducing cadmium accumulation in rice (Oryza sativa L.) grains - Wen-Ze Fang; Jun-Qiao Chen; Jing-Dong Mao; Bao-Feng Zhang; Li-Ping Lou; Qi Lin (Environmental Science and Pollution Research, 2025)

Metabolomics Revealed Cadmium Exposure Associated with Alterations in Serum Metabolism in Children - Miaoqian Li; Ping Wan; Lichun Qiao; Xinyue Wen; Huan Deng; Xue Lin; Jingke Lei; Jing Han (Biological Trace Element Research, 2025)

Crop diversity significantly enhances soil carbon sequestration via alleviating soil inorganic carbon decline caused by rhizobium inoculation - Chuan-Lin Xiao; Nai-Hao Ji; Ping Wang; Jing-Ru He; Xiang Wang; Long Li (Soil and Tillage Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Penicipyrrolizidinones A−C, three pyrrolizidinone alkaloids with unprecedented skeletons from the mangrove-derived fungus Penicillium sp. DM27 - Zhenling Chen; Jing-Jing Zhang; Cheng-Yun Huang; Wei-Chen Chen; Li-Ming He; Qing-Qing Tang; Kong-Kai Zhu; Jing Li; Ping Gao; Meng-Ke Zhang; You-Sheng Cai (Phytochemistry, 2025)

Chronic polyaluminum chloride perturbation shaped community assembly patterns: An overlooked mechanism of nitrogen removal inhibition - Nan-ping Wu; Qian Zhang; Hong-yu Wang; Yun-jie Zhang; Meng Li; Bin Ji; Yufei Bao; Bing Lin; Yu-wei Ding; Qi He; Jia-jing Chen (Chemical Engineering Journal, 2025)

Harnessing diurnal dynamics: Understanding the influence of light–dark cycle on algal-bacterial symbiotic system under aniline stress - Qi He; Qian Zhang; Meng Li; Jing He; Bing Lin; Nan-Ping Wu; Jia-Jing Chen; Xun-Hao Liu; Xiao-Qian Dong (Bioresource Technology, 2025)

Dominant spring precipitation anomaly modes and circulation characteristics in the Tarim Basin, Central Asia - Dilinuer Tuoliewubieke; Junqiang Yao; Weiyi Mao; Ping Chen; Liyun Ma; Jing Chen; Shujuan Li (Atmospheric Research, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

Heavy metal emissions from on-road vehicles in Xia-Zhang-Quan metropolitan area in southeastern China from 2015 to 2060: impact of vehicle electrification - Zhe-Nan Wen; Qi-Yu Miao; Jiang-Ru Chen; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Zhi Huang (Environmental Science and Pollution Research, 2024)

Inter-annual and spatial variations of air-sea CO2 fluxes and acidification mechanism in the coastal waters of Qingdao, China during 2011–2019 - Zheng-Xin Hu; Tie Li; Tian-Tian Ge; Jing-Wen Hu; Ping-Wang; Chun-Ying Liu; Gui-Peng Yang (Marine Pollution Bulletin, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Potential ecological risk assessment for trace metal(loid)s in soil surrounding coal gangue heaps based on source-oriented - Jie Ma; Zhijie Shen; Yue Jiang; Ping Liu; Jing Sun; Mingsheng Li; Xue Feng (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Sediment source-to-sink patterns along the southeast China coast during the late Quaternary: New insights from sediment geochemistry and OSL ages in Ningde Bay - Ping Liu; Jie Zhang; Yan Liu; Qianli Sun; Dan Zhang; Yue Li; Taoyuan Wei; Junjie Yu; Jilong Wang; Jing Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Closed-loop recycling of biodegradable poly(butylene adipate-co-terephthalate) based on hydrolysis and repolymerization strategy - Wei-Zhen Zheng; Xiao Li; Jing Xie; Ze-Yang Zhang; Ping-Li Wang; Dan Huang; Zhong-Lai Ren; Jun-Hui Ji; Ge-Xia Wang (Journal of Environmental Chemical Engineering, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Enhanced release of volatile halocarbons of microalgae in response to antibiotic-induced stress: Based on laboratory and ship-field experiments - Xiao-Yu Zhang; Li-Jing Yin; Xiao-Ping Lang; Zhen He; Gui-Peng Yang (Marine Environmental Research, 2024)

Atomic modulation of FeN4 sites on hollow carbon nanospheres by neighboring Mn atoms for ultra-stable Zn-air batteries - Zhaowei Ji; Chenglong Qiu; Ping Li; Yifan Li; Jing Shi; Jingyi Wu; Yue Zhu; Wei Hu; Zhi Li; Huanlei Wang (Chemical Engineering Journal, 2024)

Fertilization and tillage influence on soil organic carbon fractions: A global meta-analysis - Chun Liu; Chunhuan He; Scott X. Chang; Xinli Chen; Shaoshan An; Dong Wang; Jing Yan; Yuheng Zhang; Ping Li (CATENA, 2024)

Population pharmacokinetics of fluconazole for prevention or treatment of invasive candidiasis in Chinese young infants - Honghong Wang; Dandan Li; Yongjiang Jiang; Jing Liang; Qiaoai Yu; Linghong Kuang; Yuling Huang; Dongjie Qin; Ping Li; Jing He; Feng Xu; Xueli Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Inhibition of BCAT1 expression improves recurrent miscarriage by regulating cellular dysfunction and inflammation of trophoblasts - Guangli Xu; Chao Tian; Yanru Li; Lei Fang; Jing Wang; Zhuqing Jing; Simeng Li; Ping Chen (Cell and Tissue Research, 2024)

Exploring the material basis and molecular targets of Changma Xifeng tablet in treating Tourette syndrome: an integrative approach of network pharmacology and miRNA analysis - Jing Peng; Qiaoling Li; Linhui Liu; Ping Gao; Lipeng Xing; Li Chen; Hui Liu; Zhisheng Liu (Metabolic Brain Disease, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Conjugates of glycosylated antarctic krill proteins and curcumin: Maintaining the storage quality of salmon fillets coupling with photodynamic inactivation - Qiaohui Zeng; Di Hu; Yufeng Li; Ping Qi; Lu Chen; Ronghan Wang; Yong Zhao; Jing Jing Wang (Food Hydrocolloids, 2024)

Tailor-made the ultrathin nanosheet and acid site accessibility of mordenite zeolite for carbonylation of dimethyl ether - Feng Chen; Xiao-Bo Feng; Pan Deng; Li-Yun Zhang; Jing-Ping Zhao; Yu-Hui Wang; Bo-Yu Tao; Xiao-Yan Zhao; Jing-Pei Cao; Hong-Cun Bai (Chemical Engineering Journal, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Applying Novel Micro–Nano-Siliceous Grouting Material Improves Mechanical Behaviors of Fractured Rock Masses and Microscopic Characteristics of Slurry–Rock Interface: Experimental and Numerical Simulation Investigations - Jin-Peng Zhang; Ke-Sheng Li; Yang Li; Chuan-Xiao Liu; Jun-Hao Xu; Jing-Ping He (Rock Mechanics and Rock Engineering, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

A citrullinated antigenic vaccine in treatment of autoimmune arthritis - Xu Jin; Tianya Dong; Qian Wang; Yang Xie; Xiangyu Fang; Chaonan Wei; Shuyan Liu; Xi Zheng; Ping Wang; Danxue Zhu; Lulu Cao; Suwei Dong; et al. (Science Bulletin, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Aged polystyrene microplastics exposure affects apoptosis via inducing mitochondrial dysfunction and oxidative stress in early life of zebrafish - Ping Ding; Chongdan Xiang; Qian Yao; Xintong Li; Jiayi Zhang; Renli Yin; Lijuan Zhang; Adela Jing Li; Guocheng Hu (Journal of Environmental Management, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

Two pairs of new isobenzofuranone enantiomers from a soil-derived fungus Penicillium canescens DWS225 - Jing Wang; Xiao-Qian Wu; Ji-Song Mo; Yu-Fen Tan; Hong-Ping Long; Si-Qian Zhou; Shao Liu; Jing Li; Wen-Xuan Wang (Natural Product Research, 2024)

Exploring seasonal variations, assembly dynamics, and relationships of bacterial communities in different habitats of marine ranching - Cheng-Zhuang Chen; Ming-Hao Yin; Lin-Jing Niu; Jin-Xin Wang; Ling Liu; Yong-Jun Sun; Wen-Ming Ju; Ping Li; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

PKM2/Hif-1α signal suppression involved in therapeutics of pulmonary fibrosis with microcystin-RR but not with pirfenidone - Yan Ren; Jie Wang; Wen-wen Guo; Jing-wen Chen; Li-zhi Xu; Zhi-wei Wu; Ya-ping Wang (Toxicon, 2024)

The impact of CYP3A4 genetic polymorphism on crizotinib metabolism and drug-drug interactions - Jing Wang; Xiao-yu Xu; Xin-yue Li; Jian-chao Luo; Zhe-yan Zhang; Jing Chen; Jian-ping Cai; Li-kang Zhang; Jian-chang Qian (Toxicology and Applied Pharmacology, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

The complete genome sequence of the planctomycetotal bacterium Bremerella sp. P1 with abundant genes involved in polysaccharide degradation - Jia-Xuan Wang; Jing Wang; Ji-Qing Liu; Jian Li; Wen-Xin Jiang; Fei Xu; Ping-Yi Li; Qi-Long Qin; Xiu-Lan Chen; Xi-Ying Zhang (Marine Genomics, 2024)

Strengthened oil-water separation by swirl vane hydrocyclone based on short-circuit flow regulation - Wei Zhao; Jian-ping Li; Tong Zhang; Aosong Wei; Shi-yun Li; Zi-heng Zhao; Xue-jing Yang; Xia Jiang; Hua-lin Wang (Journal of Water Process Engineering, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Effects of different curing concentrations and drying times on the microbial community structure and metabolites of dried Spanish mackerel - Jing Li; Yang Liu; Cai-yan Jiang; Xiao-qing Miao; Xiu-ping Dong; Ming Du; Peng-fei Jiang (Food Chemistry, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Deciphering the influence of salinity stress on the biological aniline degradation system: Pollutants degradation performance and microbial response - Qi He; Bin Tan; Meng Li; Junhao Su; Bing Lin; Nan-ping Wu; Hao-nan Shen; Jia-jing Chen; Qian Zhang (Environmental Research, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Hydrogel membrane composite reduces fouling and retains ammonium efficiently - Ralph Rolly Gonzales; Jing Li; Pengfei Zhang; Ping Xu; Zhan Li; Mengyang Hu; Zhaohuan Mai; Kecheng Guan; Hideto Matsuyama (Environmental Chemistry Letters, 2024)
The recovery of pure water and valuable substances from wastewater is a major challenge in the context of the circular economy, requiring advanced separation methods. However, actual membrane separation techniques such as forward osmosis are limited by membrane fouling and selectivity. Here, we synthesized composite membranes by crosslinking polyvinyl alcohol hydrogel, using both glutaraldehyde and borax as crosslinking agents, on top of cellulose ester membranes. We tested these composite membranes on model and real wastewater. Results show that the composite membranes retain ammonium effectively, maintain surface electroneutrality, and exhibit remarkable resistance to fouling by organic and biological contaminants. This is explained by the high hydrophilicity of the membrane surface after application of a hydrogel layer.

Effects of miR-204-5p and Target Gene EphB2 on Cognitive Impairment Induced by Aluminum Exposure in Rats - Wei Liu; Jie Gao; Niping Hao; Jing Li; Jing Pei; Danfeng Zou; Shuo Yang; Yuhua Yin; Xiaoming Yang; Ping Mu; Lifeng Zhang (Biological Trace Element Research, 2024)

Multiple stresses induced by chronic exposure to flupyradifurone affect honey bee physiological states - Jin Chen; Yong-Jun Liu; Qiang Wang; Li Zhang; Sa Yang; Wang-Jiang Feng; Min Shi; Jing Gao; Ping-Li Dai; Yan-Yan Wu (Science of The Total Environment, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

Impact of soil density on biomineralization using EICP and MICP techniques for earthen sites consolidation - Jie Li; Feiqing Zhu; Fasi Wu; Yuxin Chen; Jenny Richards; Tianxiao Li; Ping Li; Dongjuan Shang; Jing Yu; Heather Viles; Qinglin Guo (Journal of Environmental Management, 2024)

Relish-mediated C2H2 zinc finger protein IMZF restores Drosophila immune homeostasis via inhibiting the transcription of Imd/Tak1 - Hongjian Zhou; Li Liu; Yujia Pang; Yina Xu; Jing Wu; Fei Ma; Ping Jin; Xue Zhou (Insect Biochemistry and Molecular Biology, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Autonomous, temperature-enhanced oxidase-mimic multimodal antimicrobial film for prolonged preservation of perishable products - Liang Zhang; Wen He; Yiya Ping; Wenze Wang; Puyuan Hu; Bingzhi Li; Wenxin Zhu; Jing Sun; Yanwei Ji; Jianlong Wang (Chemical Engineering Journal, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Moniezia benedeni infection increases IgE+ cells in sheep (Ovis aries) small intestine - Jing Pan; Wan-Ling Yao; Li-Ping Liu; Bao-Shan Wang; Wen-Zhu Chai; Zhen Huang; Xi-Ping Fan; Wan-Hong He; Wen-Hui Wang; Wang-Dong Zhang (Veterinary Parasitology, 2024)

Dependence of evolution of Cyanobacteria superiority on temperature and nutrient use efficiency in a meso-eutrophic plateau lake - Jing Cao; Yue Wu; Ze-kun Li; Ze-ying Hou; Tian-hao Wu; Zhao-sheng Chu; Bing-hui Zheng; Ping-ping Yang; Yi-yan Yang; Cun-sheng Li; Qian-hua Li; Xia Guo (Science of The Total Environment, 2024)

Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li-Ping Lin (Phytochemistry, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Silencing of ApCht7 and ApCht10 revealed their function and evaluation of their potential as RNAi targets in Acyrthosiphon pisum - Chunchun Li; Lixiang Wang; Lei Liu; Ning Lv; Yu-Ping Gou; Senshan Wang; Jing-Jiang Zhou; Chang-Zhong Liu (Journal of Pest Science, 2024)

Insights into growth stages and genotypes in airborne Pb accumulation in Oryza sativa L. grains: Utilizing isotope fingerprinting alongside a model study - Qi Lin; Ming-Jin Zhuang; Wei Dai; Jing Fang; Bao-Feng Zhang; Jing-Dong Mao; Li-Ping Lou (Chemosphere, 2024)

Occurrence, potential sources, and ecological risks of traditional and novel organophosphate esters in facility agriculture soils: A case study in Beijing, China - Fang Zhao; Hua Ping; Jing Liu; Tianyu Zhao; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Cheng Li (Science of The Total Environment, 2024)

FERONIA-mediated TIR1/AFB2 oxidation stimulates auxin signaling in Arabidopsis - Baiyan Lu; Shengnan Wang; Hanqian Feng; Jing Wang; Kaixing Zhang; Yilin Li; Ping Wu; Minmin Zhang; Yanshu Xia; Chao Peng; Chao Li (Molecular Plant, 2024)

Antimony and arsenic migration in a heterogeneous subsurface at an abandoned antimony smelter under rainfall - Chao Li; Yiyuan Ran; Pan Wu; Peng Liu; Boyi Yang; Xueyuan Gu; Ping Zhao; Shirong Liu; Lei Song; Yuhui Liu; Yizhang Liu; Zengping Ning; et al. (Journal of Hazardous Materials, 2024)

Innovative probiotic Escherichia coli nissle 1917-derived outer membrane vesicles coupled microspheres demonstrate anti-inflammatory and barrier-enhancing properties in colitis - Lu Han; Xu-Wei Liu; Wei-Xiong Li; Tao Zang; Zhi-Peng Li; Yao Deng; Lu-Lu Tan; Dun-Sheng Liang; Xiao-Jing Zhang; Xiao-Fan Shen; Sheng-Qiu Tang; Xiao-Ping Liao; et al. (Chemical Engineering Journal, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

Cevanine-type alkaloids from the bulbs of Fritillaria unibracteata var. wabuensis and their antifibrotic activities in vitro - Lu Fu; Wenyue Tian; Meng-Yu Bao; Zhiyan Liu; Wen-Jing Ren; Jiazheng Liu; Wei Zhang; Zhifeng Zhang; Jin Gao; Li-Ping Bai; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2024)

Nickel phosphide cocatalyst and carbon defects simultaneously boosting the photocatalytic hydrogen production over carbon nitride - ChuChang Mao; Qinghua Qu; Fada Li; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Ping Zhang; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Exosome-functionalized heterogeneous nanofibrous scaffolds repair bone defects accompanied by muscle injury - Shue Jin; Zeyu Luo; Yongrui Cai; Jing Wen; Pengyu Lu; Xiaoxue Fu; Ping Mou; Anjin Chen; Weikun Meng; Jidong Li; Zongke Zhou; Weinan Zeng (Chemical Engineering Journal, 2024)

In Vitro and In Vivo Supplementation with Curcumin Promotes Hippocampal Neuronal Synapses Development in Rats by Inhibiting GSK-3β and Activating β-catenin - Yinhong Zhang; Jinghui Yang; Yanling Gong; Shan He; Ping Wen; Yan Jiang; Jing He; Baosheng Zhu; Li Li (Molecular Neurobiology, 2024)

LiCOI1 mediates the biosynthesis of monoterpenes induced by methyl jasmonate in Lilium ‘Siberia’ - Zhuo Leng; Ying-Ying Li; Yu-Chen Fu; Jing Wu; Ping-Sheng Leng; Zeng-Hui Hu (Horticulture, Environment, and Biotechnology, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Determining buffering capacity of polydimethylsiloxane-based passive dosing for hydrophobic organic compounds in large-volume bioassays - Hao Hu; Ping Ma; Huizhen Li; Jing You (Science of The Total Environment, 2024)

Deep plowing increases soil water storage and wheat yield in a semiarid region of Loess Plateau in China: A simulation study - Xinrui Shi; Chao Li; Ping Li; Yuzheng Zong; Dongsheng Zhang; Zhiqiang Gao; Xingyu Hao; Jing Wang; Shu Kee Lam (Field Crops Research, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

CsBZR1 Family Transcription Factors in Wild and Cultural Tea Plants and Their Response to Hormone and Abiotic Stress - Jing-Wen Li; Ping Zhou; Ni Yang; Zhi-Hang Hu; Yi Chen; Wei Luo; Jie-Yu Kong; Zhi-Yuan Qin; Xing-Hui Li; Xuan Chen; Jing Zhuang (Journal of Plant Growth Regulation, 2024)

A system dynamics simulation-based strategic analysis of integrated water resources utilization and management in Shenzhen city - Guangzhi Zheng; Jing-Cheng Han; Ping Li; Bing Li; Xiaofeng Wu; Yuefei Huang; Muhammad Ahmad (Environmental Science and Pollution Research, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

Road dust exposure and human corneal damage in a plateau high geological background provincial capital city: Spatial distribution, sources, bioaccessibility, and cytotoxicity of dust heavy metals - Zi-Yue Yang; Hai Liu; Jing-Ya Li; Ya-Bo Bao; Ji Yang; Li Li; Zi-Yu Zhao; Qin-Xiang Zheng; Ping Xiang (Science of The Total Environment, 2024)

Growing-season drought and nitrogen addition interactively impair grassland ecosystem stability by reducing species diversity, asynchrony, and stability - Peng Lv; Shanshan Sun; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Ping Yue; Xiaoan Zuo (Science of The Total Environment, 2024)

Size-segregated characteristics of water-soluble oxidative potential in urban Xiamen: Potential driving factors and implications for human health - Jia-Min Li; Si-Min Zhao; Shui-Ping Wu; Bing-Qi Jiang; Yi-Jing Liu; Jie Zhang; James J. Schwab (Science of The Total Environment, 2024)

Engineering high-entropy alloy nanosheets toward efficient electrocatalytic water oxidation - Hehe Wei; Qiang Wang; Yu Zhang; Jing Li; Ping Liu; Nannan Wang; Xueqing Gong (Fuel, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Define of Optimal Addition Period of Osteogenic Peptide to Accelerate the Osteogenic Differentiation of Human Pluripotent Stem Cells - Yameng Song; Hongjiao Li; Zixuan Wang; Jiamin Shi; Jing Li; Lu Wang; Lingzi Liao; Shengqin Ma; Yun Zhang; Bin Liu; Yaling Yang; Ping Zhou (Tissue Engineering and Regenerative Medicine, 2024)

Erratum to: CD146 as a promising therapeutic target for retinal and choroidal neovascularization diseases - Bai Xue; Ping Wang; Wenzhen Yu; Jing Feng; Jie Li; Rulian Zhao; Zhenglin Yan; Xiyun Yan; Hongxia Duan (Science China Life Sciences, 2024)

Introducing fluorescent probe technology for detecting microcystin-LR in the water and cells - Bingyan Li; Zhaomin Wang; Huiyan Chuan; Jing Li; Ping Xie; Yong Liu (Analytica Chimica Acta, 2024)

Metazoan diversity and community assemblages in sediments across a Western Pacific Trench-Arc-Basin system: insights from eDNA metabarcoding - Jing Mo; Xinlong Li; Anning Mou; Ping Gao; Xuetao Wang; Xuelei Zhang; Qinzeng Xu (Frontiers in Marine Science, 2024)
Trench-arc-basin (TAB) systems are widely distributed in the deep sea, yet our understanding of their biodiversity patterns and community assemblages remains limited. In this study, we collected sediment samples from 22 stations across a Western Pacific TAB system and identified 85 families of marine benthos from 15 phyla by using eDNA metabarcoding with the 18S rRNA gene V4 region. Nematodes were the most dominant metazoan taxa followed by echinoderms, arthropods, and annelids. The highest biodiversity and species specificity were observed at stations located near seamounts. The community assemblages were highly heterogeneous in this TAB system, likely induced by the large geographic barriers and the high habitat heterogeneity. Furthermore, the total organic carbon content and median grain size of the sediment drive the overall community composition, and the water depth exerts a significant influence on species richness and abundance. Our results provide insight into benthos diversity and distribution across a TAB system and data for further comparisons and modeling studies.

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Plant composition change mediates climate drought, nitrogen addition, and grazing effects on soil net nitrogen mineralization in a semi-arid grassland in North China - Peng Lv; Shanshan Sun; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Ping Yue; Xiaoan Zuo (Science of The Total Environment, 2024)

Analyzing sulfur cycle process in natural lakes based on the combination of sulfur-producing genes and fluorescence technology - Jianping Shen; Changhui Zhang; Jing Li; Yue Zhang; Yu Hao; Ping Xie; Zhe Chen; Yong Liu (Journal of Cleaner Production, 2024)

C vacancy and F decorated g-C3N4 for boosting photocatalytic ozonation of sodium p-perfluorinated nonoxybenzenesulfonate - Weirui Chen; Siyou Fu; Xukai Li; Jing Wang; Xunan Ning; Liying Bin; Ping Li; Bing Tang; Laisheng Li (Chemical Engineering Journal, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Environmental impact and optimization suggestions of pig manure and wastewater treatment systems from a life cycle perspective - Binbin Liu; Hao Zhou; Lanfeng Li; Jing Ai; Hang He; Junxia Yu; Ping Li; Weijun Zhang (Science of The Total Environment, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Association between thermal stress and cardiovascular mortality in the subtropics - Maidina Jingesi; Shuhua Lan; Jing Hu; Mengyi Dai; Suli Huang; Siyi Chen; Ning Liu; Ziquan Lv; Jiajia Ji; Xiaoheng Li; Peng Wang; Jinquan Cheng; et al. (International Journal of Biometeorology, 2023)

Coupled simulations on fracture network evolution during nitrogen fracturing after liquid nitrogen pre-conditioning in shale - Jing Tao; Yu Wu; Shuangliang Li; Jingdong Wang; Hao Qin; Ping Wang (Bulletin of Engineering Geology and the Environment, 2023)

Experimental study on the failure mechanism of the Zhoujiashan landslide under the combined effect of rainfall and earthquake in Tianshui City, Northwest China - Jian Ren; Ping Sun; Shuai Zhang; Rongjian Li; Haojie Wang; Jing Zhang (Bulletin of Engineering Geology and the Environment, 2023)

Facilitating winter wheat sustainable intensification: Effects of two limited carbon-emission cultivation patterns in China's Huang-Huai-Hai Region - Xuechen Xiao; Juan Kang; Huawei Li; Yang Liu; Chunsheng Yao; Zhen Zhang; Ying Liu; Wan Sun; Guozhang Kang; Zhimin Wang; Chenyang Wang; Zhengbin Zhang; et al. (Agriculture, Ecosystems & Environment, 2023)

Role of APR3 in cancer: apoptosis, autophagy, oxidative stress, and cancer therapy - Ping Zhang; Chaoting Zhou; Qiangan Jing; Yan Gao; Lei Yang; Yanchun Li; Jing Du; Xiangmin Tong; Ying Wang (Apoptosis, 2023)

Dry and wet seasonal variations of the sediment fungal community composition in the semi-arid region of the Dali River, Northwest China - Xin Chen; Guoce Xu; Ping Xiong; Jianbo Peng; Kang Fang; Shun Wan; Bin Wang; Fengyou Gu; Jing Li; Haijing Xiong (Environmental Science and Pollution Research, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Biomass-derived carbon dots with light conversion and nutrient provisioning capabilities facilitate plant photosynthesis - Bingxu Cheng; Zhilin Yang; Feiran Chen; Le Yue; Xuesong Cao; Jing Li; Hai-Long Qian; Xiu-Ping Yan; Chuanxi Wang; Zhenyu Wang (Science of The Total Environment, 2023)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Co-application of chitooligosaccharides and arbuscular mycorrhiza fungi reduced greenhouse gas fluxes in saline soil by improving the rhizosphere microecology of soybean - Junqing Ma; Yi Xie; Jiali Sun; Ping Zou; Siqi Ma; Yuan Yuan; Shakeel Ahmad; Xia Yang; Changliang Jing; Yiqiang Li (Journal of Environmental Management, 2023)

Correction to: Effects of Dl-3‑n‑butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of Dl-3-n-butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Vascular cognitive impairment (VCI) has been one of the major types of cognitive impairment. Blood–brain barrier damage plays an essential part in the pathogenesis of VCI. At present, the treatment of VCI is mainly focused on prevention, with no drug clinically approved for the treatment of VCI. This study aimed to investigate the effects of DL-3-n-butylphthalide (NBP) on VCI rats. A modified bilateral common carotid artery occlusion (mBCCAO) model was applied to mimic VCI. The feasibility of the mBCCAO model was verified by laser Doppler, 13 N-Ammonia-Positron Emission Computed Tomography (PET), and Morris Water Maze. Subsequently, the Morris water maze experiment, Evans blue staining, and western blot of tight junction protein were performed to evaluate the effect of different doses of NBP (40 mg/kg, 80 mg/kg) on the improvement of cognitive impairment and BBB disruption induced by mBCCAO. Immunofluorescence was employed to examine the changes in pericyte coverage in the mBCCAO model and the effect of NBP on pericyte coverage was preliminarily explored. mBCCAO surgery led to obvious cognitive impairment and the decrease of whole cerebral blood flow, among which the blood flow in the cortex, hippocampus and thalamus brain regions decreased more significantly. High-dose NBP (80 mg/kg) improved long-term cognitive function in mBCCAO rats, alleviated Evans blue leakage and reduced the loss of tight junction proteins (ZO-1, Claudin-5) in the early course of the disease, thereby exerting a protective effect on the blood–brain barrier. No significant changes in pericyte coverage were observed after mBCCAO. High-dose NBP improved cognitive function in mBCCAO rats. High-dose NBP protected the integrity of BBB by upregulating TJ protein expression, rather than regulating pericyte coverage ratio. NBP could be a potential drug for the treatment of VCI.

Alteromonas Aquimaris sp. nov., Isolated from Surface Seawater - Qin Wang; Xin-Yuan Hu; Li-Ping Sun; Hui-Jing Niu; Cai-Xia Pei; Yi Li; Cheng-Qiang Xia (Current Microbiology, 2023)

Application of UPLC-Triple TOF-MS/MS metabolomics strategy to reveal the dynamic changes of triterpenoid saponins during the decocting process of Asian ginseng and American ginseng - Li-Hua Chen; You-Bo Zhang; Xiu-Wei Yang; Jing Xu; Zhao-Jing Wang; Yi-Zheng Sun; Wei Xu; Ying-Ping Wang (Food Chemistry, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Human TRMT1 catalyzes m2G or m22G formation on tRNAs in a substrate-dependent manner - Qing-Ping Xiong; Jing Li; Hao Li; Zhi-Xuan Huang; Han Dong; En-Duo Wang; Ru-Juan Liu (Science China Life Sciences, 2023)

Functional evaluation of CYP2C19 and CYP3A4 gene polymorphism on ibuprofen metabolism - Ling-Jing Yuan; Xiang-Yu Li; Jin-Huan Ni; Jing Wang; Xiao-Yu Xu; Jian-Chao Luo; Qi Zhou; Guo-Xin Hu; Jian-Ping Cai; Jian-Chang Qian (Toxicology and Applied Pharmacology, 2023)

Knockdown of lncRNA Meg3 delays the onset of puberty in female rats - Hailing Li; Chunhuan Ren; Juntai Lu; Shuangshuang Xu; Xinbao Gong; Wei Zhang; Xu Yan; Jing Ye; Ping Qin; Ya Liu; Yunsheng Li; Yunhai Zhang; et al. (Theriogenology, 2023)

Trade-offs between wheat soil N2O emissions and C sequestration under straw return, elevated CO2 concentration, and elevated temperature - Jing Yang; Guojun Liu; Haiyan Tian; Xin Liu; Xingyu Hao; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Aiping Wang; Ping Li; Shu Kee Lam (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Effect of safflower oil and magnetic field-modified soy 11S globulin on rheological and emulsifying properties of oil-in-water emulsions - Zhuang-Li Kang; Jing-jie Xie; Zhong-liang Hu; Yan-ping Li; Han-Jun Ma (Food Hydrocolloids, 2023)

In situ deposition of double Fe-based Fenton catalysts on the porous membrane for the development of multi-defense against various foulants toward highly efficient water purification - Yu-Ling Yang; Gang Wang; Ping Zhu; Lei Tang; Zhi-Xiang Zeng; Li-Jing Zhu (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Eight-year comparison of agroeconomic benefits of open ditch and subsurface pipe drainage in mulched drip irrigated saline–sodic farmland - Zhentao Bai; Hongguang Liu; Jing Li; Mingsi Li; Ping Gong; Pengfei Li; Ling Li (Irrigation Science, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Liver-cell protective pyridones from the fungi Tolypocladium album dws120 - Xiao-Qian Wu; Jing Li; Xi Zhou; Jing Wang; Yu-Fen Tan; Ji-Song Mo; Shao Liu; Kang-Ping Xu; Gui-Shan Tan; Wei Zhang; Wen-Xuan Wang (Phytochemistry, 2023)

Acute and chronic effects of sublethal neonicotinoid thiacloprid to Asian honey bee (Apis cerana cerana) - Min Shi; Yi Guo; Yan-Yan Wu; Ping-Li Dai; Shao-Jun Dai; Qing-Yun Diao; Jing Gao (Pesticide Biochemistry and Physiology, 2023)

Enzymatic activity of 38 CYP2C9 genotypes on ibuprofen - Ling-jing Yuan; Xiang-yu Li; Feng Ye; Xin-yue Li; Qing-qing Li; Yun-shan Zhong; Shi-yu Wang; Ya-hui Wang; Guo-xin Hu; Jian-ping Cai; Jun-wei Li (Food and Chemical Toxicology, 2023)

Constructed a self-powered sensing platform based on nitrogen-doped hollow carbon nanospheres for ultra-sensitive detection and real-time tracking of double markers - Yong-ping Gao; Ke-jing Huang; Bo-ya Wang; Qianyue Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Effects of drug-drug interactions and CYP3A4 variants on alectinib metabolism - Ya-nan Liu; Jie Chen; Jing Wang; Qingqing Li; Guo-xin Hu; Jian-ping Cai; Guanyang Lin; Ren-ai Xu (Archives of Toxicology, 2023)

Deepened snow cover increases grassland soil carbon stocks by incorporating carbon inputs into deep soil layers - Meifeng Deng; Ping Li; Weixing Liu; Pengfei Chang; Lu Yang; Zhenhua Wang; Jing Wang; Lingli Liu (Global Change Biology, 2023)
Climate‐induced changes in snow cover can greatly impact winter soil microclimate and spring water supply. These effects, in turn, can influence plant and microbial activity and the strength of leaching processes, potentially altering the distribution and storage of soil organic carbon (SOC) across different soil depths. However, few studies have examined how changes in snow cover will affect SOC stocks, and even less is known about the impact of snow cover on SOC dynamics along soil profiles. By selecting 11 snow fences along a 570 km climate gradient in Inner Mongolia, covering arid, temperate, and meadow steppes, we measured plant and microbial biomass, community composition, SOC content, and other soil parameters from topsoil to a depth of 60 cm. We found that deepened snow increased aboveground and belowground plant biomass, as well as microbial biomass. Plant and microbial carbon input were positively correlated with grassland SOC stocks. More importantly, we found that deepened snow altered SOC distribution along vertical soil profiles. The increase in SOC caused by deepened snow was much greater in the subsoil (+74.7%; 40–60 cm) than that in the topsoil (+19.0%; 0–5 cm). Additionally, the controls on SOC content under deepened snow differed between the topsoil and subsoil layers. The increase in microbial and root biomass jointly enhanced topsoil C accumulation, while the increase in leaching processes became critical in promoting subsoil C accumulation. We conclude that under deepened snow, the subsoil had a high capacity to sink C by incorporating C leached from the topsoil, suggesting that the subsoil, originally thought to be climate insensitive, could have a higher response to precipitation changes due to vertical C transport. Our study highlights the importance of considering soil depth when assessing the impacts of snow cover changes on SOC dynamics.

Four cases of reported adverse effects from black boletoi, Anthracoporus nigropurpureus (Boletaceae) mushroom ingestion - Jing Ma; Jing Xia; Hai-Jiao Li; Lin-Jie Su; Rou Xue; Shuai Jiang; Tai-Jie Yu; Yi Liu; Li-Ping Tang (Toxicon, 2023)

Photoaged microplastics induce neurotoxicity via oxidative stress and abnormal neurotransmission in zebrafish larvae (Danio rerio) - Ping Ding; Chongdan Xiang; Xintong Li; Haibo Chen; Xiaoxia Shi; Xin Li; Chushan Huang; Yunjiang Yu; Jianying Qi; Adela Jing Li; Lijuan Zhang; Guocheng Hu (Science of The Total Environment, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Integrated fixed-film activated sludge systems in continuous-flow and batch mode acclimated from low to high aniline concentrations: Performance, mechanism and metabolic pathways - Nan-ping Wu; Qian Zhang; Bin Tan; Meng Li; Bing Lin; Jing He; Jun-hao Su; Hao-nan Shen (Bioresource Technology, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Neuroprotective methylsuccinic acid and enoic acid derivatives from the fungus Xylaria longipes - Jing Li; Yu-Fen Tan; Si-Qian Zhou; Shao Liu; Wen-Xuan Wang; Yue-Ping Jiang; Hong-Ping Long; Ji-Kai Liu (Phytochemistry, 2023)

Highly sensitive detection of thiram residues on fruit peel surfaces using a filter paper-based SERS sensor with AgNWs@ZIF-8 - Nuan Xu; Zhenhua Tang; Yan-Ping Jiang; Junlin Fang; Li Zhang; Xiaofang Lai; Qi-Jun Sun; Jing-Min Fan; Xin-Gui Tang; Qiu-Xiang Liu; Ji-Kang Jian (Journal of Environmental Chemical Engineering, 2023)

Multi-scale structure characterization of ozone oxidized waxy rice starch - Jing Li; Meng Du; Zia-ud Din; Ping Xu; Lei Chen; Xi Chen; Yuehui Wang; Yang Cao; Kun Zhuang; Jie Cai; Qingyun Lyu; Xianhui Chang; et al. (Carbohydrate Polymers, 2023)

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Metabonomic Analysis of Macrobrachium rosenbergii with Iron Prawn Syndrome (IPS) - Xi-Lian Li; Pei-Jing Shen; Wen-Ping Jiang; Ji-Lun Meng; Hai-Hua Cheng; Qiang Gao (Fishes, 2023)
We previously reported on the comparison of proteomic data between seven tissue types of a novel “iron prawn” species. However, no transcripts or metabolic information are available for this species. We therefore performed shotgun LC–MS/MS metabonomic and RNA-seq analyses of the total protein from “iron prawns”. KEGG analysis revealed that the largest group consisted of a total of 114 KEGG pathway proteins, comparing the “iron prawns” with the normal prawns. A total of 423 peptides, corresponding to metabolic pathways, ABC transporters, starch and sucrose metabolism, insulin resistance/secretion, fatty digestion and absorption, and lipid metabolism, were identified. The pathways of carbohydrate and amino acid metabolism decreased in female iron prawns, while organic acid and its derivatives increased. However, the pathway of organic acid and its derivatives decreased and lipid metabolism increased in the male iron prawns. The pathways of choline metabolism in cancer and glycerophospholipid/histidine/propanoate metabolism have been significantly affected in iron prawns. Our work provides insight into the understanding of the formation mechanism of the “iron prawn”.

An overlooked influence of reactive oxygen species on ammonia-oxidizing microbial communities in redox-fluctuating aquifers - Helin Wang; Ping Li; Xiaohan Liu; Jing Zhang; Lisa Y. Stein; Ji-Dong Gu (Water Research, 2023)

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Effects of pre-emulsified safflower oil with magnetic field modified soy 11S globulin on the gel, rheological, and sensory properties of reduced-animal fat pork batter - Zhuang-Li Kang; Jing-jie Xie; Yan-ping Li; Wan-jie Song; Han-Jun Ma (Meat Science, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Recycling cinder in efficient methane production from wheat straw via solid-state anaerobic digestion (SS-AD) - Hongyi Lyu; Jing Chen; Mengyi Wang; Huaiwen Zhang; Heng Wu; Tairan Liu; Xuanmin Yang; Xiaohui Guo; Xiaojiao Wang; Ping Ai; Zhenyu Li; Minsong Lin; et al. (Chemical Engineering Journal, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Source apportionment of heavy metals in soils around a coal gangue heap with the APCS-MLR and PMF receptor models in Chongqing, southwest China - Jie Ma; Zhi-jie Shen; Sheng-lan Wang; Li Deng; Jing Sun; Ping Liu; Ze-lei She (Journal of Mountain Science, 2023)

Early–maturing cultivar of winter wheat is more adaptable to elevated [CO2] and rising temperature in the eastern Loess Plateau - Yuanling Zhang; Shu Kee Lam; Ping Li; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Jing Wang (Agricultural and Forest Meteorology, 2023)

Associations of blood metals with liver function: Analysis of NHANES from 2011 to 2018 - Wenjie Li; Xinyan Li; Jing Su; Han Chen; Ping Zhao; Haisheng Qian; Xin Gao; Qiang Ye; Guoxin Zhang; Xuan Li (Chemosphere, 2023)

Deciphering the role and mechanism of nano zero-valent iron on medium chain fatty acids production from CO2 via chain elongation in microbial electrosynthesis - Ping Wu; Jie Zhang; Jing Li; Yan Zhang; Bo Fu; Ming-Yi Xu; Yi-Feng Zhang; He Liu (Science of The Total Environment, 2023)

Di-n-butyl phthalate stress induces changes in the core bacterial community associated with nitrogen conversion during agricultural waste composting - Ping Wang; Jing Ma; Lixin Wang; Linfan Li; Xinyu Yan; Ruyi Zhang; Tomislav Cernava; Decai Jin (Journal of Hazardous Materials, 2023)

Stable isotope and elemental profiles determine geographical origin of saffron from China and Iran - Jing Nie; Jian Yang; Cuiling Liu; Chunlin Li; Shengzhi Shao; Chunxia Yao; Bilian Chen; Yi Tao; Fang Wang; Yongzhi Zhang; Karyne M. Rogers; Ping Wang; et al. (Food Chemistry, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Developing a hydroxyl-functionalized magnetic porous organic polymer combined with HPLC-MS/MS for determining 31 amide herbicides in fruit wine - Can Zhang; Shuo Li; Jing Wu; Tengteng Ping; Ling Ma; Ke Wang; Kaoqi Lian (Food Chemistry, 2023)

Effects of altered precipitation patterns on soil nitrogen transformation in different landscape types during the growing season in northern China - Peng Lv; Shanshan Sun; Xueyong Zhao; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Aixia Guo; Ping Yue; Xiaoan Zuo (CATENA, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Teleost TRAF7, a protein functions in the host antiviral responses via NF-κB and IRF3/7 mediated signaling - Peng Tian Li; Ying Li; Ying Chen; Jia Xi Zhang; Zi Hao Luo; Yi Fan Zhang; Jing Jiang; Yi Lei Wang; Zi Ping Zhang; Yong Hua Jiang; Peng Fei Zou (Frontiers in Marine Science, 2023)
Tumor necrosis factor receptor-associated factors (TRAFs) play vital roles in tumor necrosis factor receptor (TNF-R) and interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) mediated signaling pathway. However, the role that TRAF7 plays in the host immune responses is largely unknown in comparison to the extensive and in-depth research that has been conducted on other members of the TRAF family. Notably, Lc -TRAF7, a cloned TRAF7 ortholog, was discovered in the large yellow croaker ( Larimichthys crocea ) in the current study, which has an open reading frame (ORF) of 1,962 base pairs and encodes a protein of 653 amino acids (aa). Lc -TRAF7 is consisted of a RING finger domain, a coiled-coil domain, and seven WD40 domains, with the genomic organization consisted of 20 exons and 19 introns. According to the expression analysis, Lc-TRAF7 was presented in a wide range of detected organs and tissues of the healthy fish, and was able to significantly induced by stimulations of poly I:C, LPS, PGN, and Pseudomonas plecoglossicida infection. Subcellular distribution analysis revealed that Lc- TRAF7 was a cytoplasmic protein, with the RING finger and coiled-coil domain function importantly in its subcellular localization. Luciferase assays demonstrated that Lc -TRAF7 overexpression significantly induced the activation of NF-κB, IRF3, IRF7, and IFN1 promoters. In addition, the WD40 domains play a pivotal role in the NF-κB promoter activation, whereas the RING finger and coiled-coil domain were essential in the IRF3, IRF7, and IFN1 promoter activation. Notably, Lc -TRAF7 overexpression could suppress SVCV proliferation in EPC cells, and the expression levels of IRF3 , IRF7 , ISG15, ISG56 , RSAD2 , and TNF-α were up-regulated under Lc -TRAF7 overexpression in LYCMS cells. These findings collectively implied that Lc -TRAF7 may function as an important regulator in the host antiviral responses via the NF-κB as well as IRF3/7 involved signaling pathways.

Quorum sensing signals stimulate biofilm formation and its electroactivity for chain elongation: System performance and underlying mechanisms - Jing Li; He Liu; Ping Wu; Chao Zhang; Jie Zhang (Science of The Total Environment, 2023)

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

Soil particle size fractions affect arsenic (As) release and speciation: Insights into dissolved organic matter and functional genes - Qi Zou; Hang Wei; Zhiliang Chen; Ping Ye; Jianqiang Zhang; Mengqiang Sun; Ling Huang; Jing Li (Journal of Hazardous Materials, 2023)

Multi-objective optimization of winter irrigation for cotton fields in salinized freeze-thaw areas - Ling Li; Hongguang Liu; Ping Gong; En Lin; Zhentao Bai; Pengfei Li; Chunxia Wang; Jing Li (European Journal of Agronomy, 2023)

Clostridium kluyveri enhances caproate production by synergistically cooperating with acetogens in mixed microbial community of electro-fermentation system - Chao Zhang; He Liu; Ping Wu; Jing Li; Jie Zhang (Bioresource Technology, 2023)

Micropyrones A and B, two new α -pyrones from the actinomycete Microbacterium sp. GJ312 isolated from Glycyrrhiza uralensis Fisch - Ying-Ting Xu; Yu-Cai Luo; Jing-Hua Xue; Yu-Ping Li; Lei Dong; Wen-Jun Li; Zhong-Yu Zhou; Xiao-Yi Wei (Natural Product Research, 2023)

Dopaminergic Dysfunction and Glucose Metabolism Characteristics in Parkin-Induced Early-Onset Parkinson’s Disease Compared to Genetically Undetermined Early-Onset Parkinson’s Disease - Feng-Tao Liu; Jia-Ying Lu; Yi-Min Sun; Ling Li; Yu-Jie Yang; Jue Zhao; Jing-Jie Ge; Ping Wu; Jie-Hui Jiang; Jian-Jun Wu; Chuan-Tao Zuo; Jian Wang (Phenomics, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Temperature-dependent effects of neonicotinoids on the embryonic development of zebrafish (Danio rerio) - Yolina Yu Lin Wang; Yan-Er Cai; Syed Shabi Ul Hassan Kazmi; Jing Yang; Yuwen Wang; Ping Li; Wenhua Liu; Zhen Wang (Frontiers in Marine Science, 2023)
The agricultural use of neonicotinoids is increasing worldwide and poses a threat to non-target organisms. The existing toxicity data of neonicotinoids that is mainly focused on widely used neonicotinoids ignores the influence of environmental factors, like temperature, related to climate changes, etc . To fill this data gap, the present study assessed the temperature-dependent toxicity of six neonicotinoids at four temperatures. Briefly, a fish embryo toxicity test was performed at the following temperatures—20, 23, 28, and 33°C—on zebrafish embryos to evaluate the lethal and sublethal effects of these toxicants. At 28°C, the lethal toxicity (LC 50 ) values for these toxicants were cycloxaprid—3.36 mg/L, nitenpyram—7.08 mg/L, paichongding—17.2 mg/L, imidaclothiz—738.6 mg/L, dinotefuran—2,096 mg/L, and thiamethoxam—4,293 mg/L, respectively. Among the sublethal effects, the enzymatic activities changed significantly in neonicotinoid treatments, which revealed oxidative stress, metabolic disorders, and neurotoxicity. Particularly, acetylcholinesterase inhibition and glutathione S-transferase activation showed a significant dose–response relationship. However, cycloxaprid, nitenpyram, and paichongding were found to be more potent compared with imidaclothiz and thiamethoxam. The influence of temperature on these neonicotinoids demonstrated an inverted V-shaped relationship, in which toxicity decreased with the increase of temperature and then increased with the increase of temperature after exceeding the optimum temperature. This study provides a reference for the multiscale effects and potential mechanisms of neonicotinoids. Temperature-dependent toxicity is of great significance for future toxicity testing and risk assessment of chemicals in the face of global climate changes.

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Corrigendum to “CD44-targeted hyaluronic acid-curcumin prodrug protects renal tubular epithelial cell survival from oxidative stress damage” [Carbohydrate Polymers 193 (2018) 268–280] - Jing-Bo Hu; Shu-Juan Li; Xu-Qi Kang; Jing Qi; Jia-Hui Wu; Xiao-Juan Wang; Xiao-Ling Xu; Xiao-Ying Ying; Sai-Ping Jiang; Jian You; Yong-Zhong Du (Carbohydrate Polymers, 2023)

Combined nonlinear wave and current induced instantaneously-liquefied soil depth in a non-cohesive seabed - Li-Jing Yang; Fu-Ping Gao; Chang-fei Li (Coastal Engineering, 2023)

An antibody cocktail with broadened mutational resistance and effective protection against SARS-CoV-2 - Chunyun Sun; Hang Chi; Fei Yuan; Jing Li; Ji Yang; Aihua Zheng; Fei Wang; Lingling Sun; Yanjing Zhang; Ping Hu; Lihua Jiao; Yongqiang Deng; et al. (Science China Life Sciences, 2023)

Transcriptome analyses reveal the effects of mixed saline–alkali stress on indoleacetic acid and cytokinins in Malus hupehensis Rehd. leaves - Xin-Liang Wang; Ling Peng; Jian Wang; Jing-Lei Liu; Jing-Jing Jia; Li-Ping Tang (Physiology and Molecular Biology of Plants, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

Water-in-zircon: a discriminant between S- and I-type granitoid - Jing Mo; Xiao-Ping Xia; Peng-Fei Li; Christopher J. Spencer; Chun-Kit Lai; Jian Xu; Qing Yang; Ming-Dao Sun; Yang Yu; Luke Milan (Contributions to Mineralogy and Petrology, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Modulation of sea surface temperature over the North Atlantic and Indian‐Pacific warm pool on interdecadal change of summer precipitation over northwest China - Ping Wu; Yanju Liu; Yihui Ding; Xiucang Li; Jing Wang (International Journal of Climatology, 2022)
Under the background of global warming, the summer precipitation over northwest China (NW) has experienced a significant interdecadal shift since the early 1990s, followed by a great increase in precipitation. This increase was mainly due to the anomalous water vapour input from the eastern boundary, whose transport has gradually become the main moisture transport belt affecting summer precipitation over NW in the past 30 years. Further research indicates that the anomalous easterly water vapour transport mainly originates from the Arctic and North Pacific Oceans. The interdecadal increase in precipitation and changes in water vapour transport pathways are related to the interdecadal warming of the North Atlantic (NA) and Indian‐Pacific warm pool (IPWP) in the mid‐1980s. The IPWP warming potentially weakens the land–sea thermal gradient, dampens the meridional circulation in East Asia, and thereby significantly reduces the southerly water vapour transport of the Asian summer monsoon, and generates anomalous northeasterly water vapour transport from high latitudes over East Asia. Moreover, the warmer sea surface temperature (SST) over the IPWP and NA can induce an anomalous teleconnection wave train, with anomalous anticyclones over Lake Baikal and the Aleutian Islands, and an anomalous cyclone over Japan. This type of teleconnection wave train contributes to anomalous northerly winds over eastern China and easterly winds over NW. The above‐mentioned anomalous circulation favours moisture transport from both the Arctic and North Pacific toward the NW, resulting in an increase in summer precipitation associated with the anomalous regional ascending motion.

Abietane diterpenoids with neuroprotective activities from Phlegmariurus carinatus - Yang Liu; Qiang Wang; Dong-Kun Zheng; De Zhang; Zhen Xie; Jia-Wei Hu; Xin-Hua Xie; Jing Li; Shu-Ping Jiang (Natural Product Research, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Ten years of warming increased plant-derived carbon accumulation in an East Asian monsoon forest - Jing Zhang; Luhui Kuang; Zhijian Mou; Toshiaki Kondo; Jun Koarashi; Mariko Atarashi-Andoh; Yue Li; Xuli Tang; Ying-Ping Wang; Josep Peñuelas; Jordi Sardans; Dafeng Hui; et al. (Plant and Soil, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Synergistic impacts of westerlies and monsoon on interdecadal variations of late spring precipitation over the southeastern extension of the Tibetan Plateau - Jing Wang; Yanju Liu; Chengyu Song; Yihui Ding; Qiaoping Li; Ping Wu; Ying Xu; Xiangde Xu (International Journal of Climatology, 2022)
Based on multiple long‐term observational and reanalysis datasets, this study investigated the characteristics and physical mechanisms of the interdecadal variations in late spring (i.e., May) precipitation (LSP) over the southeastern extension of the Tibetan Plateau (SETP) since 1900. It was revealed that by and large, LSP over the SETP experienced interdecadal decrease during the period preceding 1927, 1962–1988, and 2004 onwards, but saw an increase during the periods of 1928–1961 and 1989–2003. The atmospheric circulations responsible for interdecadal variations in LSP over the SETP were also analysed. These analyses identified significant synergistic impacts of decreased mid‐latitude upstream westerlies and increased low‐latitude monsoonal southerlies over the Central North Bay of Bengal (CNBOB) on interdecadal variations in precipitation, suggesting striking interactions between extratropical eastward cold air and tropical northward warm/humid air. Further observational and modelling evidence suggested that Atlantic Multidecadal Oscillation (AMO) was likely to be a salient oceanic driver for the interdecadal synergy between upstream westerlies and CNBOB monsoonal southerlies. The elevated sea surface temperature anomalies associated with the warm phase of the AMO could spark favourable local atmospheric anomalies, forcing an upper‐tropospheric, planetary‐scale teleconnection emanating from the east of the North Atlantic sector, which may serve as an effective bridge linking the remote AMO signal and the synergy between westerlies and monsoonal southerlies around the SETP on interdecadal timescales. Our findings provided new insights into the understanding of the synergistic roles of westerlies and monsoons in the modulation of interdecadal LSP over the SETP, prior to the peak Asian summer monsoon season.

Typhoon-Resistant Performance Assessment of Coastal Rural Residential Keel Brick Walls Reinforced with High Ductility Concrete - Qiang Li; Jun Zhang; Rui Wang; Jing Liu; Ping Li (Journal of Marine Science and Engineering, 2022)
The keel brick wall belongs to the rural residential exterior wall unique to the southeast coastal region of China. The wooden keel inside the wall and the external tie members can improve the stability of the whole wall. However, due to the age of construction, the wooden keel inside the existing residential keel brick walls has basically rotted and lost the tie with the external members, which seriously reduces the stability of the whole wall. Moreover, the collapse of keel brick walls caused by typhoons has become more and more frequent in recent years, seriously endangering the lives and properties of residents. Therefore, it is necessary to carry out reinforcement and repair for the existing residential buildings with keel brick walls. In this paper, the keel brick walls of rural houses in Ningbo area were taken as the research object, a framework for evaluating the performance of keel brick walls against typhoons was established, tests on the lateral force resistance of keel brick walls reinforced with high ductility concrete and mortar were carried out. With the help of typhoon full-track simulation and wind field simulation technology, the 600-year near-surface typhoon wind speeds affecting Ningbo area were obtained. A joint probability distribution model of multi-directional extreme wind speed was constructed using t-Copula function to determine the mixed wind climate of Ningbo area. The extreme wind loads that keel brick walls can withstand under four types of reinforcement were finally given. The results show that the high ductility concrete reinforcement has great advantages over mortar reinforcement and avoids brittle damage of the masonry structure. The keel brick walls reinforced with single-sided mortar can withstand wind loads of a 3-year return period, the keel brick walls reinforced with single-sided high ductile concrete can withstand extreme wind loads of a 110-year return period, while the keel brick walls reinforced with double-sided mortar as well as double-sided high ductile concrete can withstand extreme wind loads of well over a 110-year return period.

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Salinimicrobium sediminilitoris sp. nov., Isolated from a Tidal Flat - Cheng-Qiang Xia; Hui-Jing Niu; Kai-Shi Dong; Li Guan; Li-Ping Sun; Qin Wang; Yan-Jiao Zhang; Yi Li; Cai-Xia Pei (Current Microbiology, 2022)

Insight to maturity during biogas residue from food waste composting in terms of multivariable interaction - Ping Chen; Lang Zhang; Yuezhong Li; Jing Liang (Environmental Science and Pollution Research, 2022)

Feasibility Studies of Nebulized SARS-CoV-2 Neutralizing Antibody in Mice and Cynomolgus Monkeys - Jilei Jia; Zhaojuan Yin; Xiao Zhang; Huimin Li; Dan Meng; Qianqian Liu; Hongfang Wang; Meng Han; Shixiang Suo; Yan Liu; Ping Hu; Chunyun Sun; et al. (Pharmaceutical Research, 2022)
Purpose Neutralizing antibodies, administrated through intravenous infusion, have shown to be highly efficacious in treating mild and moderate COVID-19 caused by SARS-CoV-2 infection in the lung. However, antibodies do not transport across the plasma-lung barrier efficiently, and up to 100 mg/kg dose was used in human causing significant supply and cost burdens. This study was to explore the feasibility of nebulized antibodies inhalation delivery as an alternative route. Methods HB27, a potent RBD-specific humanized monoclonal antibody (Zhu et al. in National Sci Rev. 8:nwaa297, 2020), showed excellent protection against SARS-CoV-2 in animal model and good safety profile in clinical studies. The pharmacokinetics and preliminary safety of HB27 administrated through the respiratory tract were studied in mice and cynomolgus monkeys here. Results At a single 5 mg/kg dose, the peak HB27 concentration in mice pulmonary epithelial lining fluid (ELF) reached 857.8 μg/mL, 670-fold higher than the PRNT 90 value of 1.28 μg/mL, and maintained above PRNT 90 over 240 h. In contrast, when administrated by intravenous injection at a 5 mg/kg dose, the antibody concentrations in mice ELF were below PRNT 90 value throughout, and were about 50-fold lower than that in the serum. In cynomolgus monkeys administrated with a single dose through inhalation, the antibody concentration in ELF remained high within 3 days. No drug-related safety concerns were observed in the studies. Conclusions The study demonstrated that nebulized neutralizing antibody delivery though inhalation could be a more efficient and efficacious alternative approach for treating COVID-19 and other respiratory infectious diseases, and warrants further evaluation in clinical studies.

Oxytocin Receptor in Cerebellar Purkinje Cells Does Not Engage in Autism-Related Behaviors - Li-Ping Shen; Wei Li; Ling-Zhu Pei; Jun Yin; Shu-Tao Xie; Hong-Zhao Li; Chao Yan; Jian-Jun Wang; Qipeng Zhang; Xiao-Yang Zhang; Jing-Ning Zhu (The Cerebellum, 2022)

Comprehensive Transcriptome Analysis of Tea Crabapple (Malus hupehensis Rehd.) Roots Subjected to Mixed Saline–Alkali Stress - Xin-Liang Wang; Ling Peng; Jian Wang; Jing-Jing Jia; Li-Ping Tang (Plant Molecular Biology Reporter, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

Sphingopyxis yananensis sp. nov., a novel 2-nitropropane degrading bacterium isolated from a microbial fermentation bed substrate - Chao-chao Zheng; Ying-ying Jiang; Tian-fei Yu; Jing Li; Jia-min Ai; Mai-ping Li; Xiao-dong Liu; Zhen-shan Deng (Archives of Microbiology, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

CD146 as a promising therapeutic target for retinal and choroidal neovascularization diseases - Bai Xue; Ping Wang; Wenzhen Yu; Jing Feng; Jie Li; Rulian Zhao; Zhenglin Yang; Xiyun Yan; Hongxia Duan (Science China Life Sciences, 2022)

Expanding the clinical spectrum of adult-onset neuronal intranuclear inclusion disease - Yuwen Cao; Jingying Wu; Yunhua Yue; Chao Zhang; Shihua Liu; Ping Zhong; Shige Wang; Xiaojun Huang; Weiping Deng; Jing Pan; Lan Zheng; Qing Liu; et al. (Acta Neurologica Belgica, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Residential proximity to major roadway and progression in physical disability in older adults in China - Jing Hu; Wenqian Chen; Lei Li; Yu Zhang; Hongwei Jiang; Wenhua Liu; Ping Yin (Environmental Science and Pollution Research, 2022)

Trichocladabiflavone A, a chalcone-flavonone type biflavonoid from Selaginella trichoclada Alsto - Yang Xie; Xiao-Chang Yao; Lei-Hong Tan; Hong-Ping Long; Ping-Sheng Xu; Jing Li; Gui-Shan Tan (Natural Product Research, 2022)

Five new phloroglucinol derivatives from Syzygium brachyantherum and their α -glucosidase and PTP1B inhibitory activities - Wen Xu; Shao-Hua Xu; Li Wang; Zhen Zang; Yan Zhao; Jing-Ping Liu; Jing Yang; Yong Zhao (Natural Product Research, 2022)

Simultaneous determination of praziquantel and its main metabolites in the tissues of black goats and their residue depletion - Tong-Yan Ding; Xiao-Gui Shu; Ren-Ping Xiong; Jing-Li Qiu; Lu Li; Li-Min He (Food Additives & Contaminants: Part A, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

Synthesis and anticancer activity of Boc-Gly-Pro dipeptide-annonaceous acetogenin prodrugs targeting fibroblast activation protein or other hydrolytic enzymes - Jing-Fang Shi; Ping Wu; Han-Xiang Li; Xiao-Yi Wei; Zi-Hua Jiang (Medicinal Chemistry Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Four new resorcinol derivatives with neuroprotective activities from Xylaria nigripes - Lan-Qing Li; Jing Li; Hong-Ping Long; Ji-Kai Liu; Xian Wang (Natural Product Research, 2022)

Transcriptomic analyses reveal the effect of nitric oxide on the lateral root development and growth of mangrove plant Kandelia obovata - Ming-Yue Wei; Huan Li; You-Hui Zhong; Zhi-Jun Shen; Dong-Na Ma; Chang-Hao Gao; Yi-Ling Liu; Wen-Hua Wang; Jing-Ya Zhang; Yan-Ping You; Hai-Lei Zheng (Plant and Soil, 2022)

Activating PIK3CA postzygotic mutations in segmental overgrowth of muscles with bone involvement in the body extremities - Wen Tian; Liying Sun; Qi Zhang; Junhui Zhao; Yang Guo; Wenyao Zhong; Liu Liu; Katia Meirelles; Sha Tang; Jing Zhang; Yingzhao Huang; Yuehan Yin; et al. (Molecular Genetics and Genomics, 2022)

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Four new prenylflavonol glycosides from the leaves of Cyclocarya paliurus - Zi-Jun Ye; Hui-Hui Sun; Zu-Hui Chen; Jian-Ping Wu; Jing Li; Hui Zhu; Lu-Lu Huang; Xi-Wen Chang; Sai-Yu Ou; Wen-Xuan Wang; Xiao-Ai He; Gang-Zhi Zhu; et al. (Natural Product Research, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Astaxanthin Ameliorates Blood Pressure in Salt-Induced Prehypertensive Rats Through ROS/MAPK/NF-κB Pathways in the Hypothalamic Paraventricular Nucleus - Hong-Li Gao; Xiao-Jing Yu; Yan Zhang; Chen-Long Wang; Yi-Ming Lei; Jia-Yue Yu; Dong-Miao Zong; Kai-Li Liu; Dong-Dong Zhang; Ying Li; Hua Tian; Nian-Ping Zhang; et al. (Cardiovascular Toxicology, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Vanillic acid combats Vibrio alginolyticus by cell membrane damage and biofilm reduction - Huan Liu; Miao Xiao; Jing Zuo; Xiaoxian He; Ping Lu; Yingyu Li; Yanni Zhao; Fei Xia (Journal of Fish Diseases, 2021)
Antibiotics are the most powerful weapon against bacterial infectious diseases in aquaculture. However, the indiscriminate usage of antibiotics often culminates in the emerging development of antibiotic‐resistant bacteria, making it imperative to search for novel types of antimicrobial agents. This study investigated the antibacterial and antivirulence effects of vanillic acid (VA) against the fish pathogen, Vibrio alginolyticus . We showed that VA had a good anti‐ Vibrio activity with minimal inhibitory concentration (MIC) of 1.0 mg/ml. In addition, VA wielded its antibacterial action in a dose‐/time‐dependent manner by causing cell membrane damage and increasing membrane permeability, which is evidenced by increasing the conductivity and malondialdehyde content in the treated cell cultures and the scanning electron microscopy images. Furthermore, VA significantly reduced the biofilm‐forming capability, mobility and exotoxin production (protease and exopolysaccharide) and downregulation of the expression of biofilm‐ and virulence‐associated genes ( sypG , fliS , fliK , lafA , lafK , asp and luxR ) was seen in the V. alginolyticus that exposed to VA at subinhibitory concentrations. Overall, our findings suggested that VA may be of interest for treating V. alginolyticus ‐associated infections in aquaculture.

Two new biflavanoids from Selaginella trichoclada Alsto - Yang Xie; Ping-Sheng Xu; Kang-Ping Xu; Zhen-Xing Zou; Gan Zhou; Dai Li; Dan Li; Xiao-Min Li; Jing Li; Gui-Shan Tan (Natural Product Research, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

MiR-590-5p inhibits pathological hypertrophy mediated heart failure by targeting RTN4 - Ping Fan; Likun Zhang; Tianyu Cheng; Jing Wang; Junyun Zhou; Li Zhao; Cuie Hua; Quan Xia (Journal of Molecular Histology, 2021)

A De Novo SEMA6B Variant in a Chinese Patient with Progressive Myoclonic Epilepsy-11 and Review of the Literature - Qian Li; Min Liu; Dan-ping Huang; Tao Li; Jing Huang; Ping Jiang; Wei-hao Ling; Xu-qin Chen (Journal of Molecular Neuroscience, 2021)

Taxonomic description of Pseudomonas rhizovicinus sp. nov., isolated from the rhizosphere of a desert shrub Haloxylon ammodendron - Ao-Lei He; Hui-Ru Li; Hui-Ping Li; Jing-Yi Gou; Jia Chen; Qi Zhao; Jin-Lin Zhang (Antonie van Leeuwenhoek, 2021)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

Phase field model for hydraulic fracture propagation in porous medium and numerical simulation analysis of hydraulic fracture propagation in a layered reservoir - Liang-Ping Yi; Chang-Xin Yang; Rui Chen; Jing-Yi Zhu; Xiao-Hua Zhu; Zhao-Zhong Yang; Xiao-Gang Li (Arabian Journal of Geosciences, 2021)

The sub-inhibitory concentration of cinnamaldehyde resists Aeromonas hydrophila pathogenicity via inhibition of W-pili production - Ping Ouyang; Jiehao Chen; Lizi Yin; Yi Geng; Defang Chen; Kaiyu Wang; Weiming Lai; Hongrui Guo; Jing Fang; Zhengli Chen; Li Tang; Chao Huang; et al. (Aquaculture International, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Characteristics of RNA alternative splicing and its potential roles in ginsenoside biosynthesis in a single plant of ginseng, Panax ginseng C.A. Meyer - Yilai Han; Lei Zhu; Li Li; Yanfang Wang; Mingzhu Zhao; Kangyu Wang; Chunyu Sun; Jing Chen; Lingyu Liu; Ping Chen; Jun Lei; Yi Wang; et al. (Molecular Genetics and Genomics, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

Emergent chikungunya fever and vertical transmission in Yunnan Province, China, 2019 - XiaoXiong Yin; Ting-Song Hu; HaiLin Zhang; YongHua Liu; ZhiJian Zhou; LeBin Liu; Ping Li; YiYin Wang; ZhaoLan Yang; Jing Yu; SiYu Chen; Fu-Qiang Zhang (Archives of Virology, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

miR-20a Promotes the Axon Regeneration of DRG Neurons by Targeting Nr4a3 - Lili Zhao; Leilei Gong; Ping Li; Jing Qin; Lingchi Xu; Qiyao Wei; Huimin Xie; Susu Mao; Bin Yu; Xiaosong Gu; Songlin Zhou (Neuroscience Bulletin, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Tyrosine kinase Fyn promotes apoptosis after intracerebral hemorrhage in rats by activating Drp1 signaling - Li Zhang; Lu Wang; Han Xiao; Hui Gan; Hui Chen; Shuyue Zheng; Dan Jian; Xuan Zhai; Ning Jiang; Zhao Jing; Ping Liang (Journal of Molecular Medicine, 2021)

Identification of Colletotrichum brevisporum causing fruit rot in yellow passion fruit (Passiflora edulis f. flavicarpa) in China - Fang Qiu; Xi Li; Chang Ping Xie; Jing Li; Fei Qing Zheng (Australasian Plant Pathology, 2021)

Comparison of Long-Term Outcomes of Endoscopic and Minimally Invasive Catheter Evacuation for the Treatment of Spontaneous Cerebellar Hemorrhage - Leiyang Li; Haixiao Liu; Jianing Luo; Zhijun Tan; Junmei Gao; Ping Wang; Wenting Jing; Ruixi Fan; Xiaoyang Zhang; Hao Guo; Hao Bai; Wenxing Cui; et al. (Translational Stroke Research, 2021)
Recently, minimally invasive techniques, including endoscopic evacuation and minimally invasive catheter (MIC) evacuation, have been used for the treatment of patients with spontaneous cerebellar hemorrhage (SCH). However, credible evidence is still needed to validate the effects of these techniques. To explore the long-term outcomes of both surgical techniques in the treatment of SCH. Fifty-two patients with SCH who received endoscopic evacuation or MIC evacuation were retrospectively reviewed. Six-month mortality and the modified Rankin Scale (mRS) score were the primary and secondary outcomes, respectively. A multivariate logistic regression model was used to assess the effects of the different surgical techniques on patient outcomes. In the present study, the mortality rate for the entire cohort was 34.6%. Univariate analysis showed that the surgical technique and preoperative Glasgow Coma Scale (GCS) score affected 6-month mortality. However, no variables were found to be correlated with 6-month mRS scores. Further multivariate analysis demonstrated that 6-month mortality in the endoscopic evacuation group was significantly lower than that in the MIC evacuation group (OR = 4.346, 95% CI 1.056 to 17.886). The 6-month mortality rate in the preoperative GCS 9–14 group was significantly lower than that in the GCS 3–8 group (OR = 7.328, 95% CI 1.723 to 31.170). Compared with MIC evacuation, endoscopic evacuation significantly decreased 6-month mortality in SCH patients. These preliminary results warrant further large, prospective, randomized studies.

Antifungal Effects of Fusion Puroindoline B on the Surface and Intracellular Environment of Aspergillus flavus - Ping-Ping Tian; Yang-Yong Lv; Ang Lv; Wen-Jing Yuan; Shuai-Bing Zhang; Na Li; Yuan-Sen Hu (Probiotics and Antimicrobial Proteins, 2021)

Differential response of microbial diversity and abundance to hydrological residual time and age in cascade reservoirs - Yihong Yue; Fushun Wang; Zhiwei Fu; Yi Tang; Jing Ma; Yong Qin; Meng Li; Ming Yang; Xue-Ping Chen (Journal of Soils and Sediments, 2021)

Altered BMP-Smad4 signaling causes complete cleft palate by disturbing osteogenesis in palatal mesenchyme - Nan Li; Jing Liu; Han Liu; Shangqi Wang; Ping Hu; Hailing Zhou; Jing Xiao; Chao Liu (Journal of Molecular Histology, 2021)

Deepened snow cover alters biotic and abiotic controls on nitrogen loss during non-growing season in temperate grasslands - Zhou Jia; Ping Li; Yuntao Wu; Sen Yang; Chengzhang Wang; Bin Wang; Lu Yang; Xin Wang; Jing Li; Ziyang Peng; Lulu Guo; Weixing Liu; et al. (Biology and Fertility of Soils, 2021)

NAC103, a NAC family transcription factor, regulates ABA response during seed germination and seedling growth in Arabidopsis - Ling Sun; Li-Ping Liu; Ya-Zhen Wang; Lei Yang; Mei-Jing Wang; Jian-Xiang Liu (Planta, 2020)

SUMOylation of Pdia3 exacerbates proinsulin misfolding and ER stress in pancreatic beta cells - Na Li; Xi Luo; Qilin Yu; Ping Yang; Zhishui Chen; Xinqiang Wang; Jipin Jiang; Jing Xu; Quan Gong; Decio L. Eizirik; Zhiguang Zhou; Jiajun Zhao; et al. (Journal of Molecular Medicine, 2020)

Groundwater resources survey of tongchuan city using the audio magnetotelluric method - Zhi-min Xu; Jing-tian Tang; Guang Li; Hui-Cui Xin; Zhang-jian Xu; Xin-ping Tan; Jin Li (Applied Geophysics, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Functional expression and characterization of an endo-1,4-β-mannosidase from Triticum aestivum in Pichia pastoris - Shuai-Bing Zhang; Wei-Ji Zhang; Na Li; Huan-Chen Zhai; Yang-Yong Lv; Yuan-Sen Hu; Jing-Ping Cai (Biologia, 2020)

Integrated biomarker parameters response to the toxic effects of high stocking density, CuSO4, and trichlorfon on fish and protective role mediated by Angelica sinensis extract - HuaTao Li; YuTing Ma; Ying Liu; Min Wu; Jiao Long; XiaoQin Jing; SiShun Zhou; Ping Yuan; Jun Jiang (Fish Physiology and Biochemistry, 2020)

A histone deacetylase, GhHDT4D, is positively involved in cotton response to drought stress - Jing-Bo Zhang; Shao-Ping He; Jing-Wen Luo; Xin-Peng Wang; Deng-Di Li; Xue-Bao Li (Plant Molecular Biology, 2020)

NLRP6 contributes to inflammation and brain injury following intracerebral haemorrhage by activating autophagy - Han Xiao; Hui Chen; Rong Jiang; Li Zhang; Lu Wang; Hui Gan; Ning Jiang; Jing Zhao; Xuan Zhai; Ping Liang (Journal of Molecular Medicine, 2020)

Sandstorm weather is a risk factor for mortality in ischemic heart disease patients in the Hexi Corridor, northwestern China - Xinghui Li; Hui Cai; Xiaolan Ren; Jin He; Jia Tang; Ping Xie; Nan Wang; Fangfei Nie; Linfeng Lei; Chenchen Wang; Wenli Li; Jing Ma (Environmental Science and Pollution Research, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Blockade of HCN2 Channels Provides Neuroprotection Against Ischemic Injury via Accelerating Autophagic Degradation in Hippocampal Neurons - Cheng Chen; Li Liu; Ya-Qiao Shu; Ping Jing; Yun Lu; Xiao-Xue Zhang; Xian-Gang Zong; Lian-Jun Guo; Chang-Jun Li (Neuroscience Bulletin, 2020)

High throughput solid-phase screening of bacteria with cyclic amino alcohol deamination activity for enantioselective synthesis of chiral cyclic β-amino alcohols - Ya-Wen Chang; Jian-Dong Zhang; Xiao-Xiao Yang; Jing Li; Li-Li Gao; Shuang-Ping Huang; Xing-Mei Guo; Cao-Feng Zhang; Hong-Hong Chang; Jian-He Xu (Biotechnology Letters, 2020)

Impacts of climate anomalies on the interannual and interdecadal variability of autumn and winter haze in North China: A review - Jing Wang; Yanju Liu; Yihui Ding; Ping Wu; Zhiwei Zhu; Ying Xu; Qiaoping Li; Yingxian Zhang; Jinhai He; Julian X. L. Wang; Li Qi (International Journal of Climatology, 2020)
From the perspectives of remote sensing and climatic factors like surface meteorological parameters, large‐scale atmospheric circulations, and external forcing factors (EFFs), the authors synthesize and review spatiotemporal variations of PM 2.5 over North China and how climate anomalies affect autumn and winter haze variability in North China according to recent studies. This review focuses on both interannual and interdecadal timescales. It is shown that circulations play an important role in influencing haze variability. Atmospheric circulations, which would be modulated by EFFs like sea surface temperature, sea ice, and snowpack, can affect the climate variability in haze over North China via modulation of surface‐layer parameters that are closely connected with the haze phenomenon. Therefore, EFFs are deemed significant factors impacting the climate variability of haze over North China, serving as paramount precursory signals for haze prediction. Furthermore, this paper suggests potential future research directions for haze variability studies in North China on the basis of summarizing and concluding the associated processes/mechanisms on how climatic factors affect haze variability, which could provide reference for treating and forecasting in situ hazy conditions.

High-level soluble expression of human Cu,Zn superoxide dismutase with high activity in Escherichia coli - Jin-Ling Yang; Xing-Lun Li; Feng-Lin Jiang; Ting Gong; Jing-Jing Chen; Tian-Jiao Chen; Ping Zhu (World Journal of Microbiology and Biotechnology, 2020)

Scientific and technological power and international cooperation in the field of natural hazards: a bibliometric analysis - Jing-Li Fan; Shuo Shen; Jian-Da Wang; Shi-Jie Wei; Xian Zhang; Ping Zhong; Hang Wang (Natural Hazards, 2020)

The bHLH gene family and its response to saline stress in Jilin ginseng, Panax ginseng C.A. Meyer - Lei Zhu; Mingzhu Zhao; Mengyao Chen; Li Li; Yue Jiang; Sizhang Liu; Yang Jiang; Kangyu Wang; Yanfang Wang; Chunyu Sun; Jing Chen; Ping Chen; et al. (Molecular Genetics and Genomics, 2020)

Circular RNA hsa_circ_0002052 promotes osteosarcoma via modulating miR-382/STX6 axis - Ping-rong Zhang; Jing Ren; Jian-shan Wan; Rong Sun; Ying Li (Human Cell, 2020)

Biofertilizers with beneficial rhizobacteria improved plant growth and yield in chili (Capsicum annuum L.) - Jing-Yi Gou; Sheng-Zhou Suo; Kun-Zhong Shao; Qi Zhao; Dan Yao; Hui-Ping Li; Jin-Lin Zhang; Christopher Rensing (World Journal of Microbiology and Biotechnology, 2020)

An Injectable Nanocomposite Hydrogel for Potential Application of Vascularization and Tissue Repair - Yilei Ding; An-sha Zhao; Tianmei Liu; Ya-nan Wang; Yuan Gao; Jing-an Li; Ping Yang (Annals of Biomedical Engineering, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

Outbreak of carp edema virus disease in cultured ornamental koi in a lower temperature in China - Ping Ouyang; Yaojia Zhou; Ruixue Yang; Zhuangzhi Yang; Kaiyu Wang; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Li Tang; et al. (Aquaculture International, 2020)

Two new phenolic glycosides from the seeds of Citrullus lanatus - Xiao-Qian Zhang; Jing Shi; Shi-Xiu Feng; Lin Xue; Li-Ping Tian (Natural Product Research, 2020)

Alternative complement pathway is activated in the brains of scrapie-infected rodents - Cao Chen; Yan Lv; Chao Hu; Xiao-Feng Xu; Ren-Qing Zhang; Kang Xiao; Yue Ma; Li-Ping Gao; Jian-Le Li; Qiang Shi; Jing Wang; Qi Shi; et al. (Medical Microbiology and Immunology, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

Identification of rs11615992 as a novel regulatory SNP for human P2RX7 by allele-specific expression - Tao Peng; Li Zhong; Jing Gao; Zhu Wan; Wei-Ping Fu; Chang Sun (Molecular Genetics and Genomics, 2020)

Comparative Serum Proteomic Analysis of the Effects of Sodium Selenate on a Mouse Model of Alzheimer’s Disease - Ping Chen; Li-Xiang Wang; Xiao-Jing Sui; Shui-Ming Li; Yong Wang; Qiong Liu; Jia-Zuan Ni (Biological Trace Element Research, 2019)

On the rapid intensification for Typhoon Meranti (2016): convection, warm core, and heating budget - Xiba Tang; Fan Ping; Shuai Yang; Mengxia Li; Jing Peng (Frontiers of Earth Science, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Identification and Characterization of ATP/ADP Isopentenyltransferases (ATP/ADP PpIPTs) Genes in Peach - Min-ji Li; Qin-ping Wei; Fu-tian Peng; Wen Yu; Jing-jing Luo; Yong-fei Zhao (Journal of Plant Growth Regulation, 2019)

The Molecular Mechanisms of Protective Role of Se on the G0/G1 Phase Arrest Caused by AFB1 in Broiler’s Thymocytes - Ke Guan; Hang Li; Zhicai Zuo; Fengyuan Wang; Ping Hu; Xi Peng; Jing Fang; Hengmin Cui; Gang Shu; Ping Ouyang (Biological Trace Element Research, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Effects of glyphosate on soybean metabolism in strains bred for glyphosate-resistance - Wei-yu Li; Ping Lu; Hao Xie; Gui-quan Li; Jing-xuan Wang; Dong-yu Guo; Xing-yu Liang (Physiology and Molecular Biology of Plants, 2019)

Clinical application of cross microsurgical vasovasostomy in scrotum for atypical obstructive azoospermia - Zhong-Yan Liang; Feng-Bin Zhang; Le-Jun Li; Jing-Ping Li; Jing-Gen Wu; Chong Chen; Yi-Min Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

Attribute recognition model for risk assessment of water inrush - Jing Wang; Shu-cai Li; Li-ping Li; Peng Lin; Zhen-hao Xu; Cheng-lu Gao (Bulletin of Engineering Geology and the Environment, 2019)

Correction to: Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Impact of surfactant and dissolved organic matter on uptake of atrazine in maize and its mobility in soil - Bing Bing Tian; Jing Hua Zhou; Fei Xie; Qian Nan Guo; Ai Ping Zhang; Xin Qiang Wang; Qian Qian Yu; Na Li; Hong Yang (Journal of Soils and Sediments, 2019)

Coexpression of FOXK1 and vimentin promotes EMT, migration, and invasion in gastric cancer cells - Hui Zhang; Xiaosheng Wu; Yizhi Xiao; Liqing Wu; Ying Peng; Weimei Tang; Guangnan Liu; Yong Sun; Jing Wang; Huiqiong Zhu; Mengwei Liu; Wenjing Zhang; et al. (Journal of Molecular Medicine, 2019)

Profiling of indole metabolic pathway in thermo-sensitive Bainong male sterile line in wheat (Triticum aestivum L.) - Qing Su; Jing Yang; Qing Yun Fu; Fei Yun Jia; Suo Ping Li; Yong Li; You Yong Li (Physiology and Molecular Biology of Plants, 2019)

Characterizing the Mass Elevation Effect across the Tibetan Plateau - Fang Han; Bai-ping Zhang; Fang Zhao; Li Wan; Jing Tan; Tian Liang (Journal of Mountain Science, 2018)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

Initial Soil Organic Matter Content Influences the Storage and Turnover of Litter, Root and Soil Carbon in Grasslands - Shan Xu; Ping Li; Emma J. Sayer; Beibei Zhang; Jing Wang; Chunlian Qiao; Ziyang Peng; Liwei Diao; Yonggang Chi; Weixing Liu; Lingli Liu (Ecosystems, 2018)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

Ore genesis of the Wusihe carbonate-hosted Zn-Pb deposit in the Dadu River Valley district, Yangtze Block, SW China: evidence from ore geology, S-Pb isotopes, and sphalerite Rb-Sr dating - Suo-Fei Xiong; Yong-Jun Gong; Shao-Yong Jiang; Xiao-Jing Zhang; Qian Li; Guo-Ping Zeng (Mineralium Deposita, 2018)

The Protective Role of Selenium in AFB1-Induced Tissue Damage and Cell Cycle Arrest in Chicken’s Bursa of Fabricius - Ping Hu; Zhicai Zuo; Fengyuan Wang; Xi Peng; Ke Guan; Hang Li; Jing Fang; Hengmin Cui; Gang Su; Ping Ouyang; Yi Zhou (Biological Trace Element Research, 2018)

New podolactones from the seeds of Podocarpus nagi and their anti-inflammatory effect - Zhe-Ling Feng; Tian Zhang; Jing-Xin Liu; Xiu-Ping Chen; Li-She Gan; Yang Ye; Li-Gen Lin (Journal of Natural Medicines, 2018)

CFTR prevents neuronal apoptosis following cerebral ischemia reperfusion via regulating mitochondrial oxidative stress - Ya-Ping Zhang; Yong Zhang; Zhi-Bin Xiao; Yan-Bo Zhang; Jing Zhang; Zhi-Qiang Li; Yao-Bin Zhu (Journal of Molecular Medicine, 2018)

The Risk Assessment of Tunnels Based on Grey Correlation and Entropy Weight Method - Cheng-lu Gao; Shu-cai Li; Jing Wang; Li-ping Li; Peng Lin (Geotechnical and Geological Engineering, 2018)

The complete mitochondrial genome of Kele pig (Sus scrofa) using next-generation deep sequencing - Ya Tan; Kai-zhi Shi; Jing Wang; Chun-lin Du; Chun-ping Zhao; Xiong Zhang; Li Zhu; Yi-shun Shang (Conservation Genetics Resources, 2018)

A new pair of enantiomeric lignans from the fruits of Morinda citrifolia and their absolute configuration - Wen-Jian Liu; Yue-Juan Chen; Dan-Na Chen; Ya-Ping Wu; Yu-Jie Gao; Jing Li; Wen-Jun Zhong; Lin Jiang (Natural Product Research, 2018)

Enhancement of the thermal and alkaline pH stability of Escherichia coli lysine decarboxylase for efficient cadaverine production - Fengyu Kou; Jing Zhao; Jiao Liu; Cunmin Sun; Yanmei Guo; Zijian Tan; Feng Cheng; Zhimin Li; Ping Zheng; Jibin Sun (Biotechnology Letters, 2018)

Genome-wide genetic variation and comparison of fruit-associated traits between kumquat (Citrus japonica) and Clementine mandarin (Citrus clementina) - Tian-Jia Liu; Yong-Ping Li; Jing-Jing Zhou; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology, 2018)

Integrated in silico–in vitro screening of ovarian cancer peroxisome proliferator-activated receptor-γ agonists against a biogenic compound library - Gui-Lian Zhang; Feng-Ying Liu; Jing Zhang; Li-Ping Wang; Er-Xia Jia; Shi-Ming Lv (Medicinal Chemistry Research, 2018)

Phenolic constituents from Rheum nobile and their antioxidant activity - Ye Fei; Juan Wang; Bing Peng; Jiangnan Peng; Jing-Hong Hu; Zu-Ping Zeng; Jing Chen; Qi-En Li; Zeng-Ping Gao; Xing-Li Yan (Natural Product Research, 2017)

RNA-seq analysis provides insight into reprogramming of culm development in Zizania latifolia induced by Ustilago esculenta - Zhi-Dan Wang; Ning Yan; Zheng-Hong Wang; Xiao-Huan Zhang; Jing-Ze Zhang; Hui-Min Xue; Li-Xia Wang; Qi Zhan; Ying-Ping Xu; De-Ping Guo (Plant Molecular Biology, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Effect of Temperature–Water Coupled Actions on Joint Morphology - Jing-shuo Liu; Ping Cao; Jie Liu; Jin-xing Fan; Guo-guo Ning; Fu-liang Li (Geotechnical and Geological Engineering, 2017)

Association between SSR markers and fibre traits in sea island cotton (Gossypium barbadense) germplasm resources - QI MA; JING ZHAO; HAI LIN; XINZHU NING; PING LIU; FUJUN DENG; AIJUN SI; JILIAN LI (Journal of Genetics, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

A potent indolylquinoline alleviates growth of human lung cancer cell tumorspheres - Yu-Ling Ni; Chang-Hung Hsieh; Seung-Hun Kim; Jing-Ping Wang; Chun-Li Su; Ching-Fa Yao; Kang Fang (Apoptosis, 2017)

Oxidative stress promotes myocardial fibrosis by upregulating KCa3.1 channel expression in AGT-REN double transgenic hypertensive mice - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Overexpression of PLK3 Mediates the Degradation of Abnormal Prion Proteins Dependent on Chaperone-Mediated Autophagy - Hui Wang; Chan Tian; Jing Sun; Li-Na Chen; Yan Lv; Xiao-Dong Yang; Kang Xiao; Jing Wang; Cao Chen; Qi Shi; Qi-Xiang Shao; Xiao-Ping Dong (Molecular Neurobiology, 2017)

A new norsesquiterpene from the roots of Polyalthia laui - Zhang-Xin Yu; Ming-Ye Zhuo; Xiao-Bao Li; Yan-Hui Fu; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han; Xin-Ming Song; Qi-Jing Fan (Natural Product Research, 2017)

Isolation and characterisation of the epothilone gene cluster with flanks from high alkalotolerant strain Sorangium cellulosum (So0157-2) - Zhi-Feng Li; Li-Ping Zhu; Jing-yan Gu; Raghvendra Pratap Singh; Yue-Zhong Li (World Journal of Microbiology and Biotechnology, 2017)

TGF-β1-miR-200a-PTEN induces epithelial–mesenchymal transition and fibrosis of pancreatic stellate cells - Min Xu; Guoying Wang; Hailang Zhou; Jing Cai; Ping Li; Meng Zhou; Ying Lu; Xiaomeng Jiang; Hongmei Huang; Youli Zhang; Aihua Gong (Molecular and Cellular Biochemistry, 2017)

Detecting the Changes of Water Qualities and Fluorescent DOM in a Constructed Rapid Infiltration System - Ping-ping Gao; Yun-zhen Li; Xu-jing Guo; Tao Huang; Dong-hai Yuan; Xian-dong Tan (Wetlands, 2017)

Carboniferous Alaskan-type complex along the Sino–Mongolian boundary, southern margin of the Central Asian Orogenic Belt - Yuruo Shi; Linlin Li; Alfred Kröner; Jing Ding; Wei Zhang; Zengbao Huang; Ping Jian (Acta Geochimica, 2017)

Interaction between southern rice black-streaked dwarf virus minor core protein P8 and a rice zinc finger transcription factor - Jing Li; Nian-Jun Cai; Jin Xue; Jian Yang; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2017)

The Brain NO Levels and NOS Activities Ascended in the Early and Middle Stages and Descended in the Terminal Stage in Scrapie-Infected Animal Models - Li-Na Chen; Jing Sun; Xiao-Dong Yang; Kang Xiao; Yan Lv; Bao-Yun Zhang; Wei Zhou; Cao Chen; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2017)

miR-200a controls hepatic stellate cell activation and fibrosis via SIRT1/Notch1 signal pathway - Jing-Jing Yang; Hui Tao; Li-Ping Liu; Wei Hu; Zi-Yu Deng; Jun Li (Inflammation Research, 2017)

Genetic characterization of H9N2 avian influenza virus in plateau pikas in the Qinghai Lake region of China - Yan Yan; Jin-Yan Gu; Zhuang-Chuan Yuan; Xin-Yu Chen; Zeng-Kui Li; Jing Lei; Bo-li Hu; Li-Ping Yan; Gang Xing; Min Liao; Ji-Yong Zhou (Archives of Virology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Organic carbon losses by eroded sediments from sloping vegetable fields in South China - Jing Qian; Li-ping Zhang; Wen-yan Wang; Qiao Liu (Journal of Mountain Science, 2017)

Di (2-ethylhexyl) phthalate impairs steroidogenesis in ovarian follicular cells of prepuberal mice - Fang-Nong Lai; Jing-Cai Liu; Lan Li; Jun-Yu Ma; Xue-Lian Liu; Yu-Ping Liu; Xi-Feng Zhang; Hong Chen; Massimo De Felici; Paul W. Dyce; Wei Shen (Archives of Toxicology, 2017)

Improvement of anti-nutritional effect resulting from β-glucanase specific expression in the parotid gland of transgenic pigs - Li-zeng Guan; Jin-shun Cai; Shuai Zhao; Yu-ping Sun; Jing-lan Wang; Yong Jiang; Gang Shu; Qing-yan Jiang; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2017)

Prolonged exposure to low-dose microcystin induces nonalcoholic steatohepatitis in mice: a systems toxicology study - Jun He; Guangyu Li; Jun Chen; Juan Lin; Cheng Zeng; Jing Chen; Junliang Deng; Ping Xie (Archives of Toxicology, 2017)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

Synergistic and Superimposed Effect of Bone Marrow-Derived Mesenchymal Stem Cells Combined with Fasudil in Experimental Autoimmune Encephalomyelitis - Jing-Wen Yu; Yan-Hua Li; Guo-Bin Song; Jie-Zhong Yu; Chun-Yun Liu; Jian-Chun Liu; Hai-Fei Zhang; Wan-Fang Yang; Qing Wang; Ya-Ping Yan; Bao-Guo Xiao; Cun-Gen Ma (Journal of Molecular Neuroscience, 2016)

Protective role of ACE2-Ang-(1–7)-Mas in myocardial fibrosis by downregulating KCa3.1 channel via ERK1/2 pathway - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2016)

In vitro remineralization of hybrid layers using biomimetic analogs - Hui-ping Lin; Jun Lin; Juan Li; Jing-hong Xu; Christian Mehl (Journal of Zhejiang University-SCIENCE B, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Treatment of SMB-S15 Cells with Resveratrol Efficiently Removes the PrPSc Accumulation In Vitro and Prion Infectivity In Vivo - Jing Wang; Bao-Yun Zhang; Jin Zhang; Kang Xiao; Li-Na Chen; Hui Wang; Jing Sun; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

The Levels of Tau Isoforms Containing Exon-2 and Exon-10 Segments Increased in the Cerebrospinal Fluids of the Patients with Sporadic Creutzfeldt-Jakob Disease - Cao Chen; Wei Zhou; Yan Lv; Qi Shi; Jing Wang; Kang Xiao; Li-Na Chen; Bao-Yun Zhang; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Advances on Bioactive Polysaccharides from Medicinal Plants - Jian-Hua Xie; Ming-Liang Jin; Gordon A. Morris; Xue-Qiang Zha; Han-Qing Chen; Yang Yi; Jing-En Li; Zhi-Jun Wang; Jie Gao; Shao-Ping Nie; Peng Shang; Ming-Yong Xie (Critical Reviews in Food Science and Nutrition, 2016)

Effect of CO 2 on Chemical and Microbial Changes of Pacific White Shrimp During Modified Atmosphere Packaging - Yun-Fang Qian; Jing Xie; Sheng-Ping Yang; Wen-Hui Wu; Qing Xiong; Zhi-Li Gao; Jian-Bing Shi (Journal of Aquatic Food Product Technology, 2016)

STAT3 signal that mediates the neural plasticity is involved in willed-movement training in focal ischemic rats - Qing-ping Tang; Qin Shen; Li-xiang Wu; Xiang-ling Feng; Hui Liu; Bei Wu; Xiao-song Huang; Gai-qing Wang; Zhong-hao Li; Zun-jing Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Neuropeptide S ameliorates olfactory spatial memory impairment induced by scopolamine and MK801 through activation of cognate receptor-expressing neurons in the subiculum complex - Yu-Feng Shao; Can Wang; Jun-Fan Xie; Xiang-Pan Kong; Le Xin; Chao-Yu Dong; Jing Li; Wen-Ting Ren; Yi-Ping Hou (Brain Structure and Function, 2016)

Changes and characteristics of dissolved organic matter in a constructed wetland system using fluorescence spectroscopy - Yuan Yao; Yun-zhen Li; Xu-jing Guo; Tao Huang; Ping-ping Gao; Ying-pei Zhang; Feng Yuan (Environmental Science and Pollution Research, 2016)

Genetic polymorphism analyses of a novel panel of 19 X-STR loci in the Chinese Uygur ethnic minority - Yu-xin Guo; Jian-gang Chen; Yan Wang; Jiang-wei Yan; Jing Chen; Tian-hua Yao; Li-ping Zhang; Guang Yang; Hao-tian Meng; Yu-dang Zhang; Ting Mei; Yao-shun Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Adverse effect of DEHP exposure on the serum insulin level of Balb/c mice - Jing Wang; Jinquan Li; Kashif Rafiq Zahid; Kun Wang; Yan Qian; Ping Ma; Shumao Ding; Xu Yang; Xianliang Wang (Molecular & Cellular Toxicology, 2016)

Single-nucleotide polymorphisms in the PLA2R1 gene are associated with systemic lupus erythematosus and lupus nephritis in a Chinese Han population - Yuan Li; Aihong Zhou; Guanting Lv; Ping Li; Si Chen; Jing Li; Xiaoting Wen; Ziyan Wu; Shulan Zhang; Jibo Wang; Fengchun Zhang; Yongzhe Li (Immunologic Research, 2016)

Positive association of genetic variations in the phospholipase C-like 1 gene with dermatomyositis in Chinese Han - Qian Wang; Si Chen; Yuan Li; Ping Li; Chanyuan Wu; Ziyan Wu; Qingjun Wu; Fei Sun; Jing Li; Wenjie Zheng; Chuiwen Deng; Fengchun Zhang; et al. (Immunologic Research, 2016)

Photodegradation of Mefenamic Acid in Aqueous Media: Kinetics, Toxicity and Photolysis Products - Ping Chen; Feng Liang Wang; Kun Yao; Jing Shuai Ma; Fu Hua Li; Wen Ying Lv; Guo Guang Liu (Bulletin of Environmental Contamination and Toxicology, 2016)

Remarkable Activation of the Complement System and Aberrant Neuronal Localization of the Membrane Attack Complex in the Brain Tissues of Scrapie-Infected Rodents - Yan Lv; Cao Chen; Bao-Yun Zhang; Kang Xiao; Jing Wang; Li-Na Chen; Jing Sun; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2015)

Effects of miRNA-145 on airway smooth muscle cells function - Yun Liu; Xiuzhen Sun; Yuanyuan Wu; Ping Fang; Hongyang Shi; Jing Xu; Manxiang Li (Molecular and Cellular Biochemistry, 2015)

Assessment of Sediment Risk in the North End of Tai Lake, China: Integrating Chemical Analysis and Chronic Toxicity Testing with Chironomus dilutus - Hongxue Qi; Ping Ma; Huizhen Li; Jing You (Archives of Environmental Contamination and Toxicology, 2015)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Retraction Note to: Relationships between PON1 Q192R polymorphism and clinical outcome of antiplatelet treatment after percutaneous coronary intervention: a meta-analysis - Ping Li; Shu-Hong Bu; Xiao-Tong Lu; Li-Xia Li; A-Jing Xu; Yue-Nian Tang; Jian Zhang (Molecular Biology Reports, 2015)

Cloning of the Aegiceras corniculatum class I chitinase gene (AcCHI I) and the response of AcCHI I mRNA expression to cadmium stress - Li-Ying Wang; You-Shao Wang; Hao Cheng; Jing-Ping Zhang; Foong Swee Yeok (Ecotoxicology, 2015)

Molecular cloning of class III chitinase gene from Avicennia marina and its expression analysis in response to cadmium and lead stress - Li-Ying Wang; You-Shao Wang; Jing-Ping Zhang; Ji-Dong Gu (Ecotoxicology, 2015)

Anti-inflammatory effect of procyanidin B1 on LPS-treated THP1 cells via interaction with the TLR4–MD-2 heterodimer and p38 MAPK and NF-κB signaling - Jing Xing; Rui Li; Nan Li; Jian Zhang; Yueqing Li; Ping Gong; Dongna Gao; Hui Liu; Yu Zhang (Molecular and Cellular Biochemistry, 2015)

Roles of Serine/Threonine Phosphatases in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Jing Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Generation and characterization of Brassica rapa ssp. pekinensis – B. oleracea var. capitata monosomic and disomic alien addition lines - AI XIA GU; SHU XING SHEN; YAN HUA WANG; JIAN JUN ZHAO; SHU XIN XUAN; XUE PING CHEN; XIAO FENG LI; SHUANG XIA LUO; YU JING ZHAO (Journal of Genetics, 2015)

Identification of volatile and softening-related genes using digital gene expression profiles in melting peach - Xiong-wei Li; Jun Jiang; Li-ping Zhang; Yi Yu; Zheng-wen Ye; Xiu-min Wang; Jing-yi Zhou; Ming-liang Chai; Hui-qin Zhang; Pere Arús; Hui-juan Jia; Zhong-shan Gao (Tree Genetics & Genomes, 2015)

ERK5 signalling pathway is essential for fluid shear stress-induced COX-2 gene expression in MC3T3-E1 osteoblast - Jin Jiang; Liang-gong Zhao; Yuan-jun Teng; Shao-long Chen; Li-ping An; Jing-ling Ma; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2015)

Foxl2 of the Hong Kong catfish (Clarias fuscus): cDNA cloning, tissue distribution and changes in gene expression towards methyltestosterone, estradiol and letrozole exposure of the fries during gonadal differentiation - Si-ping Deng; Chun-hua Zhu; Jing Sun; Wen-da Wang; Tian-li Wu; Hua-pu Chen; Shang-li Shi; Guang-li Li (Genes & Genomics, 2015)

Pure total flavonoids from Citrus paradisi Macfadyen act synergistically with arsenic trioxide in inducing apoptosis of Kasumi-1 leukemia cells in vitro - Bo Wang; Sheng-yun Lin; Ying-ying Shen; Li-qiang Wu; Zhen-zhen Chen; Jing Li; Zhi Chen; Wen-bin Qian; Jian-ping Jiang (Journal of Zhejiang University-SCIENCE B, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

P5-2 of rice black-streaked dwarf virus is a non-structural protein targeted to chloroplasts - Xiao-Ya Liu; Jian Yang; Li Xie; Jing Li; Xi-Jiao Song; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Scrapie Infection in Experimental Rodents and SMB-S15 Cells Decreased the Brain Endogenous Levels and Activities of Sirt1 - Jing Wang; Jin Zhang; Qi Shi; Bao-Yun Zhang; Cao Chen; Li-Na Chen; Jing Sun; Hui Wang; Kang Xiao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

Impact of MDM2 Single Nucleotide Polymorphism on Oral Squamous Cell Carcinoma Risk - Jian-Li Xie; Jing-Lei Yang; De-Sheng Liu; Yong-Gang Xie; Ping Ji (Cell Biochemistry and Biophysics, 2015)

Genetic diversity and evolution of two capsid protein genes of citrus tristeza virus isolates from China - Guan-Wei Wu; Min Tang; Guo-Ping Wang; Feng-Yin Jin; Zuo-Kun Yang; Li-Jing Cheng; Ni Hong (Archives of Virology, 2015)

Transcriptome Profiling Identified Multiple Jasmonate ZIM-Domain Proteins Involved in the Regulation of Alkaloid Biosynthesis in Tobacco BY-2 Cells - Yuping Yang; Jing Guo; Pengcheng Yan; Yunshuang Li; Kun Liu; Ping Gao; Heping Zhao; Yubao Chen; Yingdian Wang; Michael P. Timko; Shengcheng Han (Plant Molecular Biology Reporter, 2015)

Characterization of homologous and heterologous interactions between viroplasm proteins P6 and P9-1 of the fijivirus southern rice black-streaked dwarf virus - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Li Xie; Jian-Ping Chen (Archives of Virology, 2015)

Responses of canola (Brassica napus L.) cultivars under contrasting temperature regimes during early seedling growth stage as revealed by multiple physiological criteria - Jing Zhang; Fangwei Jiang; Ping Yang; Jing Li; Guijun Yan; Liyong Hu (Acta Physiologiae Plantarum, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Secretory expression of a bispecific antibody targeting tumor necrosis factor and ED-B fibronectin in Pichia pastoris and its functional analysis - Meng-yuan Liu; Xue-ping Hu; Mian Xie; Si-jing Jiang; Lu-jun Li; Dong-xu Liu; Xiao-song Yang (Biotechnology Letters, 2014)

A prepared anti-MSTN polyclonal antibody reverses insulin resistance of diet-induced obese rats via regulation of PI3K/Akt/mTOR&FoxO1 signal pathways - Liang Tang; Chen-tao Liu; Xu-dan Wang; Kai Luo; Di-di Zhang; Ai-ping Chi; Jing Zhang; Li-jun Sun (Biotechnology Letters, 2014)

The Adhesion AND Growth of Both the Human Primary Gingival Epithelial Cells and Streptococcus Mutans on Micro-Arc Oxidized Titanium - Jiangning Lv; Hongwei Li; Ying Mu; ShuMin Wang; Jing Sun; Jun Jiang; Ping Ding; Baolin Liu (Cell Biochemistry and Biophysics, 2014)

Expression and localization of transcription factors SNAIL and SLUG in mouse ovaries and pre-implantation embryos - Cui Guo; Xiaoqian Meng; Jing Bai; Cheng Chen; Tao Liu; Shuzhen Liu; Cong Zhang; Wei-Ping Li (Cell and Tissue Research, 2014)

Analysis of small RNAs derived from Chinese wheat mosaic virus - Jian Yang; Shi-Ling Zheng; Heng-Mu Zhang; Xiao-Ya Liu; Jing Li; Jun-Min Li; Jian-Ping Chen (Archives of Virology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

RETRACTED ARTICLE: Relationships between PON1 Q192R polymorphism and clinical outcome of antiplatelet treatment after percutaneous coronary intervention: a meta-analysis - Ping Li; Shu-Hong Bu; Xiao-Tong Lu; Li-Xia Li; A-Jing Xu; Yue-Nian Tang; Jian Zhang (Molecular Biology Reports, 2014)

Genetic Diversity and Population Structure of Seedling Populations of Pyrus pashia - Yu Zong; Ping Sun; Jing Liu; Xiaoyan Yue; Kunming Li; Yuanwen Teng (Plant Molecular Biology Reporter, 2014)

Sequence and phylogenetic analysis of surface protein genes of emerging H9N2 influenza viruses isolated from poultry in two geographical regions of China - Yu Xue; Jing-Lan Wang; Zhuan-Qiang Yan; Guang-Wei Li; Shun-Yan Chen; Xiang-Bin Zhang; Jian-Ping Qin; Hai-Yan Li; Shuang Chang; Feng Chen; Ying-Zuo Bee; Qing-Mei Xie (Virus Genes, 2014)

Bayesian uncertainty analysis in hydrological modeling associated with watershed subdivision level: a case study of SLURP model applied to the Xiangxi River watershed, China - Jing-Cheng Han; Guo-He Huang; Hua Zhang; Zhong Li; Yong-Ping Li (Stochastic Environmental Research and Risk Assessment, 2014)

miRNAs expression profile in bast of ramie elongation phase and cell wall thickening and end wall dissolving phase - Jun Wang; Jing-shu Huang; Xin-yan Hao; Yan-ping Feng; Ya-Jun Cai; Li-qin Sun (Molecular Biology Reports, 2014)

Coal-burning endemic fluorosis is associated with reduced activity in antioxidative enzymes and Cu/Zn-SOD gene expression - Qi Wang; Kang-ping Cui; Yuan-yuan Xu; Yan-ling Gao; Jing Zhao; Da-sheng Li; Xiao-lei Li; Hou-jin Huang (Environmental Geochemistry and Health, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Effects of watershed subdivision level on semi-distributed hydrological simulations: case study of the SLURP model applied to the Xiangxi River watershed, China - Jing-Cheng Han; Guo-He Huang; Hua Zhang; Zhong Li; Yong-Ping Li (Hydrological Sciences Journal, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Further studies on Toxascaris leonina (Linstow, 1902) (Ascaridida: Ascarididae) from Felis lynx (Linnaeus) and Panthera leo (Linnaeus) (Carnivora: Felidae) - Li-Mei Xue; Jing-Bo Chai; Yan-Ning Guo; Lu-Ping Zhang; Liang Li (Acta Parasitologica, 2014)
Toxascaris leonina (Linstow, 1902) is a most common intestinal parasite of various animals in Felidae and Canidae. In the present paper, light and scanning electron microscopy (SEM) were used to study the morphological aspects of adult worms of this nematode in detail, based on the material collected from Panthera leo (Linnaeus) and Felis lynx (Linnaeus) (Carnivora: Felidae) in China. The results showed that there were some morphometric differences between the present material and the previous studies, including the body size, the width and length of cervical alae, the number of denticles on each lip and the tail length of the female. Previously unreported morphological features were also revealed. These supplementary morphological and morphometric data contributed to a more accurate identification of this worldwide distributed ascarid nematode.

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Interaction Between AT1 Receptor and NF-κB in Hypothalamic Paraventricular Nucleus Contributes to Oxidative Stress and Sympathoexcitation by Modulating Neurotransmitters in Heart Failure - Xiao-Jing Yu; Yu-Ping Suo; Jie Qi; Qing Yang; Hui-Hua Li; Dong-Mei Zhang; Qiu-Yue Yi; Jian Zhang; Guo-Qing Zhu; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Design, synthesis and antidepressant activity evaluation 2′-hydroxy-4′,6′-diisoprenyloxychalcone derivatives - Li-Ping Guan; Dong-Hai Zhao; Yue Chang; Yu Sun; Xiao-Li Ding; Jing-Fei Jiang (Medicinal Chemistry Research, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

IgG-Fc N-glycosylation at Asn297 and IgA O-glycosylation in the hinge region in health and disease - Jing Xue; Li-Ping Zhu; Qiang Wei (Glycoconjugate Journal, 2013)

The HTLV-1 HBZ protein inhibits cyclin D1 expression through interacting with the cellular transcription factor CREB - Yunyun Ma; Shangen Zheng; Yuanyuan Wang; Wenqiao Zang; Min Li; Na Wang; Ping Li; Jing Jin; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Erratum to: Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Association of TGF-β1 +869C/T promoter polymorphism with susceptibility to autoimmune diseases: a meta-analysis - Li Zhang; Jun-wei Yan; Ying-Xin Wang; Ya-nan Wan; Jian-ping Li; Ping Liu; Bin Xu; Bing-xiang Wang; Wen-jia Peng; Fa-ming Pan; Jing Wang (Molecular Biology Reports, 2013)

MJO change with A1B global warming estimated by the 40-km ECHAM5 - Ping Liu; Tim Li; Bin Wang; Minghua Zhang; Jing-jia Luo; Yukio Masumoto; Xiaocong Wang; Erich Roeckner (Climate Dynamics, 2013)

β-Glucanase specific expression in the parotid gland of transgenic mice - Li-zheng Guan; Yu-ping Sun; Qian-yun Xi; Jing-lan Wang; Jun-yun Zhou; Gang Shu; Qing-yan Jiang; Yong-liang Zhang (Transgenic Research, 2013)

Interactions between the P6 and P5-1 proteins of southern rice black-streaked dwarf fijivirus in yeast and plant cells - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Ming-Fang Lv; Li Xie; Yuan Meng; Pei-Pei Li; Jian-Ping Chen (Archives of Virology, 2013)

Molecular characterization and phylogenetic analysis of infectious bursal disease viruses isolated from chicken in South China in 2011 - Di Liu; Xiang-Bin Zhang; Zhuan-Qiang Yan; Feng Chen; Jun Ji; Jian-Ping Qin; Hai-Yan Li; Jun-Peng Lu; Yu Xue; Jia-Jia Liu; Qing-Mei Xie; Jing-Yun Ma; et al. (Tropical Animal Health and Production, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

β-receptor blocker influences return of spontaneous circulation and chemical examination in rats during cardiopulmonary resuscitation - Xiao-jing Zhao; Zhuo Pen; Ping Li; Er-xiu Chen; Jian Liu; Yan-xia Gao; Yun-xia Ren; Li-jun Li (Journal of Zhejiang University-SCIENCE B, 2013)

Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Genetic structure and phylogeography of Pyrus pashia L. (Rosaceae) in Yunnan Province, China, revealed by chloroplast DNA analyses - Jing Liu; Ping Sun; Xiaoyan Zheng; Daniel Potter; Kunming Li; Chunyun Hu; Yuanwen Teng (Tree Genetics & Genomes, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

Small water clusters stimulate microcystin biosynthesis in cyanobacterial Microcystis aeruginosa - Jing Wang; Feng Zhao; Baihua Chen; Yanni Li; Ping Na; Jian Zhuo (Journal of Applied Phycology, 2013)

The confirmation of three repeated sequence elements in the 3′ untranslated region of Chikungunya virus - Yu Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Yin-Hui Yang; Qing-Yu Zhu (Virus Genes, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Tetramethylpyrazine induces G0/G1 cell cycle arrest and stimulates mitochondrial-mediated and caspase-dependent apoptosis through modulating ERK/p53 signaling in hepatic stellate cells in vitro - Feng Zhang; De-Song Kong; Zi-Li Zhang; Na Lei; Xiao-Jing Zhu; Xiao-Ping Zhang; Li Chen; Yin Lu; Shi-Zhong Zheng (Apoptosis, 2013)

Negative transcriptional regulation of inflammatory genes by group B3 vitamin nicotinamide - Xiao-Ming Zhang; Yu-Ping Jing; Meng-Ying Jia; Li Zhang (Molecular Biology Reports, 2012)

Rapid odor perception in rat olfactory bulb by microelectrode array - Jun Zhou; Qi Dong; Liu-jing Zhuang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Enhanced overall resistance to Fusarium seedling blight and Fusarium head blight in transgenic wheat by co-expression of anti-fungal peptides - Zheng-Wei Liu; He-Ping Li; Wei Cheng; Peng Yang; Jing-Bo Zhang; An-Dong Gong; Yan-Ni Feng; W. G. Dilantha Fernando; Yu-Cai Liao (European Journal of Plant Pathology, 2012)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

Iridoids from the roots of Valeriana jatamansi and their biological activities - Jing Xu; Ping Guo; Yuanqiang Guo; Lingzhi Fang; Yushan Li; Zhanping Sun; Liping Gui (Natural Product Research, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

The key role of PGC-1α in mitochondrial biogenesis and the proliferation of pulmonary artery vascular smooth muscle cells at an early stage of hypoxic exposure - Jingjing Rao; Jing Li; Yun Liu; Ping Lu; Xiaojiao Sun; P. K. Sugumaran; Daling Zhu (Molecular and Cellular Biochemistry, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Identification of a new Bombyx mori nucleopolyhedrovirus and analysis of its bro gene family - Jing-Bo Zhou; Xing-Qi Li; Wanchai De-Eknamkul; Siripuk Suraporn; Jia-Ping Xu (Virus Genes, 2012)

Dysregulation of the β3 integrin-VEGFR2 complex in Hantaan virus–directed hyperpermeability upon treatment with VEGF - Wei Wang; Ye Zhang; Yu Li; Lei Pan; Lu Bai; Yan Zhuang; Chang-Xing Huang; Jiu-Ping Wang; Hai-Tao Yu; Xin Wei; Wei Jiang; Ya-Yun Nan; et al. (Archives of Virology, 2012)

EGFR-mediated G1/S transition contributes to the multidrug resistance in breast cancer cells - Shu-Jun Chen; Jing Luan; Hai-Shi Zhang; Can-Ping Ruan; Xin-Yun Xu; Qing-Quan Li; Nian-Hong Wang (Molecular Biology Reports, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Chemical and pharmacological studies of Oplopanax horridus, a North American botanical - Tyler Calway; Guang-Jian Du; Chong-Zhi Wang; Wei-Hua Huang; Jing Zhao; Shao-Ping Li; Chun-Su Yuan (Journal of Natural Medicines, 2012)

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

Physiological responses to salt stress of T2 alfalfa progenies carrying a transgene for betaine aldehyde dehydrogenase - Li-Ping Yan; Cui-Lan Liu; Hui-Min Liang; Xiu-Hong Mao; Fei Wang; Cai-Hong Pang; Jing Shu; Yang Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Microsporogenesis, microgametogenesis, and pollen morphology of Ambrosia artemisiifolia L. in China - Jia-Xi Liu; Min Wang; Bing-Xiao Chen; Ping Jin; Jing-Yu Li; Ke Zeng (Plant Systematics and Evolution, 2012)

Determination of aflatoxins in edible oil from markets in Hebei Province of China by liquid chromatography–tandem mass spectrometry - Li-xin Yang; Yin-ping Liu; Hong Miao; Bin Dong; Na-jing Yang; Feng-qi Chang; Li-xue Yang; Jing-bo Sun (Food Additives & Contaminants Part B-Surveillance, 2011)

APE1 Asp148Glu gene polymorphism and lung cancer risk: a meta-analysis - Ya-Nan Ji; Ping Zhan; Jing Wang; Li-Xin Qiu; Li-Ke Yu (Molecular Biology Reports, 2011)

Transumbilical single-port laparoscopic cholecystectomy using traditional laparoscopic instruments: a report of thirty-six cases - Li-ping Cao; Ri-sheng Que; Fan Zhou; Guo-ping Ding; De-xi Jing (Journal of Zhejiang University-SCIENCE B, 2011)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Induction of somatic embryogenesis from female flower buds of elite Schisandra chinensis - Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Dimethyl sulfoxide induces heme oxygenase-1 expression via JNKs and Nrf2 pathways in human umbilical vein endothelial cells - Chao Liang; Zhanggang Xue; Jing Cang; Hao Wang; Ping Li (Molecular and Cellular Biochemistry, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Ds-echinoside A, a new triterpene glycoside derived from sea cucumber, exhibits antimetastatic activity via the inhibition of NF-κB-dependent MMP-9 and VEGF expressions - Qin Zhao; Zhi-dong Liu; Yong Xue; Jing-feng Wang; Hui Li; Qing-juan Tang; Yu-ming Wang; Ping Dong; Chang-hu Xue (Journal of Zhejiang University-SCIENCE B, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Glycomyces halotolerans sp. nov., a novel actinomycete isolated from a hypersaline habitat in Xinjiang, China - Tong-Wei Guan; Zhan-Feng Xia; Jing Xiao; Nan Wu; Zheng-Jun Chen; Li-Li Zhang; Xiao-Ping Zhang (Antonie van Leeuwenhoek, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Investigation of the microRNAs in safflower seed, leaf, and petal by high-throughput sequencing - Haiyan Li; Yuanyuan Dong; Yepeng Sun; Erle Zhu; Jing Yang; Xiuming Liu; Ping Xue; Yanshuang Xiao; Shulin Yang; Jinyu Wu; Xiaokun Li (Planta, 2011)

Development, characterization, and cross-species/genera transferability of SSR markers for rubber tree (Hevea brasiliensis) - Fei Yu; Bao-Hua Wang; Su-Ping Feng; Jing-Yi Wang; Wei-Guo Li; Yao-Ting Wu (Plant Cell Reports, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

TNF-308 gene polymorphism is associated with COPD risk among Asians: meta-analysis of data for 6,118 subjects - Ping Zhan; Jing Wang; Shu-Zhen Wei; Qian Qian; Li-Xin Qiu; Li-Ke Yu; Yong Song (Molecular Biology Reports, 2011)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Involvement of Hepatopoietin Cn in the development of human hepatocellular carcinoma - Bu-Dong Zhu; Xiao-Li Li; Yong Liu; Jing Chang; Yang Liu; Dong-Dong Zhang; Qiang Wang; Jun Ren; Chun-Ping Cui (Clinical & Experimental Metastasis, 2010)

FLT3 and NPM1 mutations in Chinese patients with acute myeloid leukemia and normal cytogenetics - Lei Wang; Wei-lai Xu; Hai-tao Meng; Wen-bin Qian; Wen-yuan Mai; Hong-yan Tong; Li-ping Mao; Yin Tong; Jie-jing Qian; Yin-jun Lou; Zhi-mei Chen; Yun-gui Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Remote chlorophyll- a retrieval in Case-II waters using an improved model and IRS-P6 satellite data - Jing-Ping Xu; Fang Li; Bai Zhang; Xing-Fa Gu; Tao Yu (International Journal of Remote Sensing, 2010)

High-frequency somatic embryogenesis from germinated zygotic embryos of Schisandra chinensis and evaluation of the effects of medium strength, sucrose, GA3, and BA on somatic embryo development - Ai Hua Chen; Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Chang Yeon Yu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Isolation and characterization of a gene encoding a polyethylene glycol-induced cysteine protease in common wheat - Qing-Wei Zang; Cai-Xiang Wang; Xu-Yan Li; Zhi-Ai Guo; Rui-Lian Jing; Jun Zhao; Xiao-Ping Chang (Journal of Biosciences, 2010)

Do local communities support the conservation of endangered Przewalski’s gazelle? - Junhua Hu; Xiaoge Ping; Jing Cai; Zhongqiu Li; Chunwang Li; Zhigang Jiang (European Journal of Wildlife Research, 2010)

Induction and origin of adventitious roots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Shi-Jie Chai; Li-Ping Chen; Ming-Fang Zhang; Jing-Quan Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Unique evolutionary pattern of numbers of gramineous NBS–LRR genes - Jing Li; Jing Ding; Wen Zhang; Yuanli Zhang; Ping Tang; Jian-Qun Chen; Dacheng Tian; Sihai Yang (Molecular Genetics and Genomics, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Spatial and seasonal characterization of net primary productivity and climate variables in southeastern China using MODIS data - Dai-liang Peng; Jing-feng Huang; Alfredo R. Huete; Tai-ming Yang; Ping Gao; Yan-chun Chen; Hui Chen; Jun Li; Zhan-yu Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Prediction of summer grain crop yield with a process-based ecosystem model and remote sensing data for the northern area of the Jiangsu Province, China - Weimin Ju; Ping Gao; Yanlian Zhou; Jing M. Chen; Shu Chen; Xianfeng Li (International Journal of Remote Sensing, 2010)

ThPOD3, a truncated polypeptide from Tamarix hispida, conferred drought tolerance in Escherichia coli - Xiao-Hong Guo; Jing Jiang; Bai-Chen Wang; Hui-Yu Li; Yu-Cheng Wang; Chuan-Ping Yang; Gui-Feng Liu (Molecular Biology Reports, 2010)

Quantitative prediction of channel sand bodies based on seismic peak attributes in the frequency domain and its application - Lu-Ping Sun; Xiao-Dong Zheng; Hao Shou; Jing-Song Li; Yan-Dong Li (Applied Geophysics, 2010)

Isolation of a new glycoside from starfish, Asterias amurensis Lutken, and its stimulation activity on the proliferation of the UMR106 cell - Hong-Wei Liu; Jian-Kuan Li; Da-Wei Zhang; Jing-Chao Zhang; Xue Zhang; Xiao-Hong Song; Ying Xia; Nai-Li Wang; Xin-Sheng Yao; Guo-Ping Cai (Natural Product Research, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Effects of cefotaxime and kanamycin on thallus proliferation and differentiation in Porphyra yezoensis and their inhibition on Agrobacterium tumefaciens - Ping Wang; Gang Wang; Yajuan Teng; Xinshu Li; Jing Ji; Xinghong Xu; Yongzhong Li (Marine Biology Research, 2010)

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells - Chen-Jing Wang; Chang-Ping Hu; Kang-Ping Xu; Qiong Yuan; Fu-Shuang Li; Hui Zou; Gui-Shan Tan; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Isolation and Characterization of a Microsporocyte-Specific Gene, OsMSP, in Rice - Dagang Jiang; Jing Li; Ping Wu; Zhenlan Liu; Chuxiong Zhuang (Plant Molecular Biology Reporter, 2009)

Fluorocurcumins as Cyclooxygenase-2 Inhibitor: Molecular Docking, Pharmacokinetics and Tissue Distribution in Mice - Subhash Padhye; Sanjeev Banerjee; Deepak Chavan; Shubhangini Pandye; K.Venkateswara Swamy; Shadan Ali; Jing Li; Q. Ping Dou; Fazlul H. Sarkar (Pharmaceutical Research, 2009)

Reciprocal regulation between M3 muscarinic acetylcholine receptor and protein kinase C-ε in ventricular myocytes during myocardial ischemia in rats - Peng-zhou Hang; Jing Zhao; Yu-ping Wang; Li-hua Sun; Yong Zhang; Li-li Yang; Na Zhao; Zhi-dan Sun; Yu-ying Mao; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Molecular alteration of Cav1.2 calcium channel in chronic myocardial infarction - Ping Liao; Guang Li; De Jie Yu; Tan Fong Yong; Jue Jin Wang; Jing Wang; Tuck Wah Soong (Pflügers Archiv - European Journal of Physiology, 2009)

Selection of scFvs specific for the HepG2 cell line using ribosome display - Lei Zhou; Wei-Ping Mao; Juan Fen; Hong-Yun Liu; Chuan-Jing Wei; Wen-Xiu Li; Feng-Yun Zhou (Journal of Biosciences, 2009)

A value chain approach to crisis response system: the case of Qingdao - Jian Hua Li; Zheng Ping Zhang; Rui Huan Jing; Chong Fu Huang (Stochastic Environmental Research and Risk Assessment, 2009)

Association of polymorphisms at restriction enzyme recognition sites of apolipoprotein B and E gene with dyslipidemia in children undergoing primary nephrotic syndrome - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Feng Ying Lei; Ping Chen; Ming Fang Li (Molecular Biology Reports, 2009)

BREVIS RADIX is involved in cytokinin-mediated inhibition of lateral root initiation in Arabidopsis - Jing Li; Xiaorong Mo; Jirong Wang; Nannan Chen; Huan Fan; Chunyan Dai; Ping Wu (Planta, 2009)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

Vimentin is required for dengue virus serotype 2 infection but microtubules are not necessary for this process - Wei Chen; Na Gao; Jia-li Wang; Yan-ping Tian; Zong-tao Chen; Jing An (Archives of Virology, 2008)

Solid lipid nanoparticles loading adefovir dipivoxil for antiviral therapy - Zhang Xing-guo; Miao Jing; Li Min-wei; Jiang Sai-ping; Hu Fu-qiang; Du Yong-zhong (Journal of Zhejiang University-SCIENCE B, 2008)

Genetic Diversity and Systematic Evolution of Chinese Domestic Ducks Along the Yangtze-Huai River - Tang-jie Zhang; Hui-fang Li; Kuan-wei Chen; Hong Chang; Qing-ping Tang; Jing-xin Zhang (Biochemical Genetics, 2007)

Genomic analysis of a Chinese isolate of Getah-like virus and its phylogenetic relationship with other Alphaviruses - Jin-Sheng Wen; Wen-Zhong Zhao; Jian-Wei Liu; Hong Zhou; Jian-Ping Tao; Hui-Jun Yan; Yu Liang; Jing-Jiao Zhou; Li-Fang Jiang (Virus Genes, 2007)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Across Genus Plasmid Transformation Between Bacillus subtilis and Escherichia coli and the Effect of Escherichia coli on the Transforming Ability of Free Plasmid DNA - Xiaojuan Wang; Meiju Li; Qing Yan; Xiangdong Chen; Jing Geng; Zhixiong Xie; Ping Shen (Current Microbiology, 2007)

Adaptive Evolution of the First Extra Exon in the Murid Rodent Prolactin Gene Family - Ying Li; Jing-Fei Huang; Ya-Ping Zhang (Biochemical Genetics, 2007)

Pathogenesis of Parkinson’s disease: oxidative stress, environmental impact factors and inflammatory processes - Hong Yuan; Jing-Chen Zheng; Ping Liu; Shao-Feng Zhang; Jian-Yang Xu; Li-Min Bai (Neuroscience Bulletin, 2007)

Isolation of Female-Specific AFLP Markers and Molecular Identification of Genetic Sex in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Jing Li; Si-Ping Deng; Yong-Sheng Tian; Qing-Yin Wang; Zhi-Meng Zhuang; Zhen-Xia Sha; Jian-Yong Xu (Marine Biotechnology, 2007)

Phenolic constituents from the rhizomes of Gastrodia elata - Xiao-Dong Yang; Jie Zhu; Rong Yang; Jing-Ping Liu; Liang Li; Hong-Bin Zhang (Natural Product Research, 2007)

Identification of poly-reactive natural IgM antibody that recognizes late apoptotic cells and promotes phagocytosis of the cells - Meng Fu; Ping-shen Fan; Wei Li; Cheng-xin Li; Ying Xing; Jing-gang An; Gang Wang; Xue-li Fan; Tian-wen Gao; Yu-feng Liu; Shigaku Ikeda (Apoptosis, 2007)

Receptor-mediated gene delivery using polyethylenimine (PEI) coupled with polypeptides targeting FGF receptors on cells surface - Da Li; Qing-qing Wang; Gu-ping Tang; Hong-liang Huang; Fen-ping Shen; Jing-zhong Li; Hai Yu (Journal of Zhejiang University-SCIENCE B, 2006)

Expression of cysteine sulfinate decarboxylase (CSD) in male reproductive organs of mice - Jian Hua Li; Ya Qin Ling; Jing Jing Fan; Xiao Ping Zhang; Sheng Cui (Histochemistry and Cell Biology, 2006)

Identification and expression analysis of alternatively spliced isoforms of human interleukin-23 receptor gene in normal lymphoid cells and selected tumor cells - Xiang-Yue Zhang; Hai-Jing Zhang; Yun Zhang; Ying-Jie Fu; Jie He; Li-Ping Zhu; Shu-Hui Wang; Li Liu (Immunogenetics, 2006)

Study on the expression and mutation of human telomeric repeat binding factor (hTRF1) in 10 malignant hematopoietic cell lines - Jie Sun; He Huang; Yuan-yuan Zhu; Jian-ping Lan; Jing-yuan Li; Xiao-yu Lai; Jian Yu (Journal of Zhejiang University-SCIENCE B, 2005)

Approach to the regionalization of agricultural-pasturalization around changshan islands in northern yellow sea - Yao-guang Zhang; Li-jing Dong; Chun-ping Li (Chinese Geographical Science, 2002)

Monoclonal anti-androgen receptor antibodies: Production, characterization, and potential diagnostic applications - Charles C.-Y. Smith; Win-Jing Young; Chi-Huei Wang; Li-Ping Jin; Xiang-Dong Ji; Qi Guan; Min Wang; Chawnshang Chang (Molecular and Cellular Biochemistry, 1999)